Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

High efficiency water evaporation and purification performance of three-dimensional porous graphene oxide based photothermal evaporators - Qiao Wu; Saihong Ru; Mengxin Wang; Xiaoyu Zheng; Hao Cheng; Maoqing Fan; Wang Li (Chemical Engineering Journal, 2026)

Accumulation, elimination and biotransformation of paralytic shellfish toxins in ark shell Anadara kagoshimensis - Zhuo-Ru Lin; Hui-Xia Geng; Sara A. Cunha; Chang Xu; Ren-Cheng Yu (Marine Pollution Bulletin, 2026)

Complete mitochondrial genomes and phylogenetic analysis of three species of Indo-Pacific freshwater gobies, Stiphodon (Gobiiformes, Oxudercidae) - Cheng-He Sun; Xian-Ru Li; Su-Fan Zhou; Yan-Zi Zhong; Xiao Ma; Xiao-Die Chen (Journal of Genetics, 2026)

Targeting microglial TLR3–NF-κB/MAPK and JAK/STAT Axis: PEITC as a suppressor of poly (I:C)-induced neuroinflammation - Yi-Ching Lan; Yan-Ru Xiao; Yow-Wen Hsieh; Yih-Dih Cheng; Shu-Fen Peng; Fu-Shin Chueh; Hsu-Tung Lee; Yu-Sheng Hsieh; Wei-Cheng Jiang; Wen-Tsong Hsieh; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

Phylogenomics, reticulate evolution, and taxonomic revision of East Asian Cardamine (Brassicaceae) in the Hengduan biodiversity hotspot - Jia-lu Li; Dan-hui Liu; Jiang-lin Miao; Yi He; Liao-cheng Zhao; Di Zhang; Ke-ping Ma; Quan-ru Liu (Molecular Phylogenetics and Evolution, 2026)

Construction of Brick-Wall-Like Topological Olefin-Linked Covalent Organic Frameworks via a Steric-Hindrance-Mediated Strategy for Efficient Uranium Capture - Cheng-Peng Niu; Rui Zhang; Zhi-Hai Peng; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2026)

A gully catchment-scale model for predicting loess cave density: a case study from the Loess Plateau - Xiaolei Gao; Haopeng Geng; Meiqin Han; Wanying Xu; Ru Liu; Weiming Cheng; Baotian Pan (CATENA, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Galectin-3 in systemic lupus erythematosus: a meta-analysis - Yang Wu; Li-Na Jiang; Jing-Ru Wu; Yi-Ran Lu; Ting-ting Lu; Ji-Min Zhu; Jing Li; Shanshan Xu; Bai-Kun Li; Cheng-Gui Miao; Yan-Mei Mao (Immunologic Research, 2026)

Different mucosal immunity and hormonal responses to routine physical training in the follicular and the luteal phases of elite female athletes - Chung-Kai Wang; Cheng-Shiun He; Ming-Ru Chiang; Pei-Ying Li; Chun-Wei Wang; Liang-You Chen; Shih-Hua Fang (European Journal of Applied Physiology, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Cadmium disrupts the immune antibacterial function of the freshwater crab Sinopotamon henanense via the Toll/proPO-AS pathway - Yue Liang; Duwen Pei; Cheng Liu; Fenjun Yan; Minnan Bao; Na Liu; Qian Wang; Caiping Feng; Ru Jia; Lan Wang (Journal of Hazardous Materials, 2026)

Two stages of Sn enrichment in granitic magmatism: insights from Sn isotopes of cogenetic minerals - Jia-Xin She; Weiqiang Li; Ru-Cheng Wang; Lei Xie; Chen Liu; Zhihao Xu; Shichao An; Cheng Xu (Geochimica et Cosmochimica Acta, 2026)

A multi-strategy incorporated artificial bee colony algorithm for multi-AGV scheduling with downtime failure - Maodi Ru; Peng Duan; Yao Cheng; Wenqiang Zou; Kaizhou Gao (Journal of Cleaner Production, 2026)

Ozone-mediated microbial succession and kinetic for refrigerated grass carp (Ctenopharyngodon idella) fillets - Cheng Guo; Guodong Xu; Shanbai Xiong; Tao Yin; Ru Liu; Juan You (International Journal of Food Microbiology, 2026)

Numerical and experimental study on the soot formation in methane multi-jet flames under microgravity - Wen-Jiao Wang; Kai-Ru Jin; Zhi-Hao Zheng; Hong-Qing Shi; Du Wang; Ling-Nan Wu; Ya-Wen Liu; Longfei Li; Jiayu Sun; Yu Cheng Liu; Zhen-Yu Tian (Fuel, 2026)

Non-enzymatic electrochemical determination of the food-related biogenic amine serotonin using a reduced graphene oxide/organic–inorganic Copper(I) phosphate composite - Asit Kumar Panda; Tzu-Yuan Sung; Wan-Ju Lu; Yi-Ru Cheng; Wen-Hui Fang; Chih-Min Wang (Food Bioscience, 2026)

Constructing compatible LLZTO/PEO interfaces with fast Li+ transport channels for high-performance composite polymer electrolytes - Yimei Jin; Yiting Lin; Zekai Zhang; Bing Li; Ru Wang; Cheng Lian; Xia Han; Honglai Liu; Haiping Su; Jingkun Li (Chemical Engineering Journal, 2026)

Synchronized lignocellulosic pyrolysis for activator-free carbon foams: Role of selective hemicellulose removal - Jia-Cheng Ye; Xiao-Ru Meng; Bo Xia; Ting-Yu Bi; Wei Chen; Lu-jiang Xu; Shuai Gao; Zhen Fang (Journal of Environmental Chemical Engineering, 2026)

Persimmon tannin: a novel green enhancer for dual improvement of texture and digestibility in surimi gels - Jingzhi Yan; Shiren Zhang; Kaile Chen; Yanxu Zhuang; Yiyi Cheng; Yan Xu; Ru Song; Haiyan Gao (Food Chemistry, 2026)

Predation, Climate and Species Traits Interact to Shape Global Patterns of Avian Nest Architecture - Stephanie Y. Chia; Yu Tsai‐Chen; Yi‐Ru Cheng; Mao‐Ning Tuanmu; William F. Fagan (Global Ecology and Biogeography, 2026)
Aim Bird nest structures are critical for reproductive success and vary widely across species. However, the ecological and evolutionary drivers behind enclosed nests (domes and cavities) remain unclear, with previous studies yielding conflicting results. Leveraging recently available comprehensive nest trait data, we aim to clarify whether enclosed nests primarily function as protection from predation or for regulation of microclimate. Location Global. Time Period Contemporary (environmental data from 1981 to 2010). Major Taxa Studied Birds (Aves). Methods Using phylogenetic logistic regression models for 7427 bird species, we examined whether the observed relationships between nest structure and potential environmental drivers and species traits were consistent with the predictions of the two functional hypotheses. To explore potential variations in the function, we built separate models for domes and cavities, as well as for passerines and non‐passerines. Results Predation risk increases the likelihood of dome use, especially in passerines, where a stronger increase is among the species that are more susceptible to nest predation such as ground‐nesting, non‐cooperative and larger clutch size species. Climatic effects are more pronounced in cavity nesters, with aridity promoting cavity use among passerines, and both cold and hot temperatures increasing cavity use among small non‐passerine species. Main Conclusions Different types of enclosed nests correspond to distinct environmental challenges, with dome nests primarily associated with predation pressure and cavities with adverse climatic conditions. These findings contribute to resolving long‐standing debates about the functional significance of enclosed nests and offer insights into the evolution of avian nest structures.

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

Multiprotein-based nanomedicines with dual CD44/CD133 targeting and GSH-responsive drug release for improving cancer chemotherapy - Lu-Yi Yu; Pei-Wei Shueng; Yu-Hsin Wang; Yu-Wei Yen; Kuan-Wei Chen; Chieh-Ru Li; Hsin-Cheng Chiu; Yu-Wen Lin; Chun-Liang Lo (Drug Delivery and Translational Research, 2026)
Albumin, a highly biocompatible protein, has been utilized in the construction of anti-cancer drugs for the treatment of various cancers. However, albumin-based nanomedicines still face several clinical challenges, including low stability in the bloodstream, non-specific targeting ability, and lack of controlled release capability. To address these limitations, we developed a multiprotein-based nanomedicine for targeted chemotherapy of non-small cell lung cancer (NSCLC). This nanomedicine was assembled using a heart-shaped albumin and two Y-shaped anti-CD44 and anti-CD133 antibodies. To enhance stability and improve therapeutic efficacy, the multiproteins were crosslinked using disulfide bond linkers and loaded with paclitaxel and ceramide. This resulted in nanomedicines that exhibited responsiveness to glutathione (GSH) and demonstrated inhibition of tumor cancer cells and cancer stem cells (CSCs). Our experimental results indicated that the inclusion of anti-CD44 and anti-CD133 antibodies enhanced the targeting capability of nanomedicines towards cancer cells and CSCs in an in vitro study and the accumulation in both normoxic regions and hypoxic niches in in vivo tumor xenografts. The multiprotein-based nanomedicines also demonstrated GSH-dependent drug release behavior, induced apoptosis in cancer cells and CSCs, inhibited cell migration, and effectively suppressed NSCLC tumor growth. Overall, our findings presented a novel nanostructure created from differently shaped proteins for application in drug delivery. This multiprotein-based nanomedicines showed promising potential in addressing the limitations of albumin-based nanomedicines and may offer improved therapeutic outcomes for cancer treatment. Graphical Abstract

Integrative morphological and genomic analyses reveal diversity, reticulate evolution, and adaptation in diploid and tetraploid Rosa species from Xinjiang - Zhongyu Tang; Zhenlong Liang; Hengning Deng; Liangying Li; Jian Ru; Shiqi Li; Jia Miao; Cheng Zhang; Xinfen Gao (Molecular Phylogenetics and Evolution, 2026)

Synergistic inhibition of advanced glycation end products and enhancement of flavor by the combination of oligomeric proanthocyanidins and glycated yeast proteins - Jing-jing Fu; Bo-wen Ru; Qi-cheng Zhang; Yu-jun Wu; Hai-yang Feng; Lian-ping Zheng; Yue-wen Chen (Food Research International, 2026)

Harnessing Rhizopus oligosporus mycelium as a sustainable protein source: Functional properties and optimization of a meat-analogue “chicken popcorn” - Bao-Hong Lee; Ru-Yi Ferng; Hao-Yuan Chien; Cheng-Hao Huang; Wei-Hsuan Hsu (Food Hydrocolloids, 2026)

Single-cell transcriptomics reveal PRRC1 as a malignant cell enriched driver of DNA repair and therapy resistance in glioblastoma - Sachin Kumar; Ming-Cheng Tsai; Dahlak Daniel Solomon; Juan Lorell Ngadio; Do Thi Minh Xuan; Ching-Chung Ko; Hung-Yun Lin; Meng-Chi Yen; I-Jeng Yeh; Yung-Kuo Lee; Hui-Ru Lin; Jian-Ying Chuang; et al. (DNA Repair, 2026)

Distinguishing the contributions of organic matter and iron (oxyhydr)oxides to zinc availability in paddy soils surrounding lead-zinc mines - Yecheng Li; Zebin Hong; Yan Ru; Guojun Chen; Xiaomin Li; Shiwen Hu; Yang Yang; Chao Guo; Shan Wang; Pengfei Cheng; Qi Wang; Tongxu Liu (Environmental Pollution, 2026)

Constructing diverse spinel/V2CTx heterostructures with tailored interfacial electron coupling for efficient oxygen evolution reaction - Li Dong; Shuang Li; Min Hu; Keke Li; Ya-Pan Wu; Xue-Qian Wu; Guangtong Hai; Cheng-Bin Zhong; Ru-an Chi; Dong-Sheng Li (Chemical Engineering Journal, 2026)

Long-term intercropping increases soil aggregate stability by altering soil colloid content and stability - Chuan-Lin Xiao; Jing-Ru He; Cheng-Bao Wang; Wei-Ping Zhang; Jun Mao; Peter Christie; Jian-Ying Shang; Long Li (Plant and Soil, 2026)

Triterpenoids from Ganoderma angustisporum and their α -glucosidase inhibitory activities - Fan-Ru Xu; Le Zhou; Yu-Cheng Dai; Hai-Sheng Yuan; Yu-Xi Wang (Natural Product Research, 2026)

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Enantioselective photoenolization/Diels–Alder reaction catalyzed by chiral Brønsted acid - Bin-Xian Chen; Xiang-Kui He; Bao-Ru Yuan; Liang-Qiu Lu; Ying Cheng; Wen-Jing Xiao (Science Bulletin, 2026)

Multi-source remote sensing for spatial mapping of salt-affected agricultural soils in Taiwan - Nguyen-Thanh Son; Chein-Hui Syu; Chi-Farn Chen; Cheng-Ru Chen; Huan-Sheng Lin; Yi-Ting Zhang; Tsang-Sen Liu; Chun-Chien Yen (Applied Geomatics, 2026)

Research progress on chemical constituents and biological activities of medicinal plants from Euonymus genus - Ying-Jun Ma; Xin-Ru Li; Meng-Qi Gao; Jia-Jia Liu; Ammara Khalid; Jie-Ting Chen; Fan-Cheng Meng (Natural Product Research, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Ti(IV)-incorporated covalent organic frameworks for efficient dark-photocatalytic reduction of U(VI) - Li-Ling Chen; Cheng-Peng Niu; Rui Zhang; Yun-Peng Wu; Zhen-Wen Zhang; Bin Lin; Cheng-Rong Zhang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2026)

Synergistic one-step pyrolysis of waste coffee grounds and orange peels: A green route to hierarchical porous carbon for high-performance supercapacitors - Yu-Cheng Chang; Shao-Ru Chang (Journal of Environmental Chemical Engineering, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

APMAP regulated by YY1 transcription mediates ferroptosis and metastasis in non-small cell lung cancer through the PI3K/AKT/mTOR pathway - Xiaohong Zhuang; Shu Lin; Cheng-sheng zhang; Qi Qin; Qixing Yan; Jing-ru Luo; Wenjun Tang (Journal of Molecular Histology, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Optimizing the spatial configuration of scallop suspended cultivation net cages by leveraging seston flux variables based on the lattice Boltzmann hydrodynamics - Gangqin Tu; Haifei Liu; Zhiming Ru; Tao Sun; Wei Yang; Wei Huang; Li Cheng (Aquaculture, 2026)

Spatio-seasonal distribution, precursor transformation, and ecological risks of per- and polyfluoroalkyl substances in port sediments: Insights from a subtropical urban harbor - Chih-Feng Chen; Noralyn G. Dimaongon; Yun-Ru Ju; Chiu-Wen Chen; Yee Cheng Lim; Ming-Huang Wang; Cheng-Di Dong (Regional Studies in Marine Science, 2026)

Integrated assessment of trace element enrichment and accumulation in estuarine sediments of southwestern Taiwan using Sr/Ba ratios and pollution indices - Chih-Feng Chen; Noralyn G. Dimaongon; Yee Cheng Lim; Ming-Huang Wang; Yun-Ru Ju; Kent Naiah D. Araña; Chiu-Wen Chen; Cheng-Di Dong (Regional Studies in Marine Science, 2026)

Ecological impacts and sustainable development of offshore wind farm pile foundations in the Bodhi Island area - Xiaochen Cheng; Ting Wang; Zhaoming Gao; Xu Wang; Shuai Liu; Yongchao Hu; Beini Deng; Libin Zhang; Xiaoshang Ru (Marine Environmental Research, 2026)

Autophagy, ROS, and their interplay in plant adaptive responses - Chi Zhang; Song-Qi Li; Pengwei Jing; Run-Xin Wu; Yu-Qing Ma; Ji-Xiao Wu; Ru-Feng Song; Wen-Cheng Liu (Journal of Plant Physiology, 2026)

A dramatic drop in Nb solubility during fractional crystallization of carbonatites triggers Nb ore formation - Ya-Ting Xu; Ru-Cheng Wang; Xu-Dong Che; Fabrice Gaillard; Marion Louvel; Giada Iacono-Marziano; Johann Tuduri (Geochimica et Cosmochimica Acta, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

Fluorescent aptasensor based on magnetic bead–assisted displacement reaction for monitoring vancomycin in plasma - Cheng-Shiuan Hsieh; Hsu-Yun Tsai; Ting-Chien Tsai; Yang-Chun Wang; Yi-Tung Cheng; Jing-Ru Liou; Meng-Yu Liu; Yen-Ling Chen; Chien-Chin Chen (Analytica Chimica Acta, 2026)

Designing light-guiding carriers in microalgal-bacterial systems: From optimization to integration and development perspectives - Cong-Cong Tang; Jin-Qiao Liu; Yong-Qi Cheng; Ya-Ru Hu; Zhang-Wei He; Wen-Qiong Wang; Zhi-Hua Li; Xiaochang C. Wang; Yu Tian (Chemical Engineering Journal, 2025)

A Transformer-based framework with generative spectral augmentation for online monitoring of hyaluronic acid fermentation - Weilu Tian; Lixuan Zang; Yunyi Li; Cheng Peng; Jinhua Zhang; Huarong Shao; Ruiqing Xian; Ru Sun; Fei Liu; Haining Tan; Peixue Ling (Carbohydrate Polymers, 2025)

GZR101, a Novel Premixed Insulin for the Treatment of Diabetes Mellitus - Wei Chen; Cheng Cui; Wancai Xing; Yining Zhang; Anshun He; Yue Wang; Yan Huang; Nannan Zhai; Qimin Shi; Fangkai Xue; Yongchun Wang; Jun Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Characterization of the complete mitogenomes of Synodontis decorus and Synodontis petricola (Teleostei: Mochokidae) with a phylogenetic analysis of the Mochokidae family - Cheng-He Sun; Xian-Ru Li; Yi-Jing Zhan; Chang-Hu Lu (Molecular Genetics and Genomics, 2025)

Complete mitochondrial genome sequence of Nannostomus eques and comparative analysis with Nannostomus beckfordi - Xian-Ru Li; Cheng-He Sun; Yi-Jing Zhan; Shuang-Xi Jia; Chang-Hu Lu (Molecular Genetics and Genomics, 2025)

Impact of vancomycin and Clostridioides difficile on the secretome and pathogenicity of Clostridium innocuum - Yi-Ywan M. Chen; Kun-Yi Chien; Hui-Ru Shieh; Cai-Jie Luo; Yu-Xun Chang; Chuan Chiang-Ni; Chih-Ho Lai; Cheng-Hsun Chiu (Medical Microbiology and Immunology, 2025)

Side-chain design approach for au-immobilized electroactive poly(amic acid) as magnetically recyclable catalyst toward rapid 4-nitrophenol reduction - Yi-Sheng Chen; Wei-Zhong Shi; Mei-Hui Tsai; Jie-Ru Lee; Cheng-Yi Xie (Journal of Water Process Engineering, 2025)

A Li-ion permeable poly(phenylene ether-ether-sulfone) interphase to address interfacial instability and structural degradation of Ni-rich NCM cathodes in poly(ethylene oxide)-based all-solid-state Li-ion batteries - Cheng-Hung Liao; Yu-Ting Weng; Senthil-Kumar Parthasarathi; Hsi Chen; Shu-Jui Chang; Guan-Yi Liu; Tsung-Yu Yu; Chih-Wen Pao; Ting-Shan Chan; Wei-Tsung Chuang; Chun-Chieh Wang; Ru-Jong Jeng; et al. (Chemical Engineering Journal, 2025)

The new ten-numbered macrolide, diaporthsin L, from endophytic fungus Diaporthe sp. G-4 isolated from Strobilanthes cusia (Nees) Kuntze - Jun-yi Li; Zhen-xian Cun; Hui-hui Sun; Jie-Zheng Shi; Wen-xiang Yan; Jun-meng Xia; Dong Gan; Mao-ru Li; Ju-cheng Zhang; Zhong-tao Ding (Natural Product Research, 2025)

Unraveling the enrichment mechanisms of U, Re, Se and V in the Bayinqinggeli Deposit, Northern Ordos Basin through in situ mineralogical analysis - Xiao-Wen Hu; Ming-Xing Ling; Jian-Bing Xu; Fei Xia; De-Ru Xu; Ya-Lun Li; Xiao-Yong Yang; Chao Lu; Hua-Ming Li; Zhen-Cheng Li; Long-Hui Wang; Feng Zhang; et al. (Journal of Geochemical Exploration, 2025)

Multi-omics insights into micro-oxygen-regulated microbial decolorization and metabolic pathways during hydrolysis and acidification of textile wastewater - Jiehui Ren; Qian Peng; Zhejun Du; Xiaoxin Yang; Jiayao Hui; Ru Li; Wen Cheng (Journal of Cleaner Production, 2025)

Sequential fermentation with Kluyveromyces marxianus and yogurt starter cultures produces stirred fermented milk with reduced lactose and enhanced natural flavor - Yu-Ting Feng; Yan-Ru Zhou; Chang-Cheng Li; Shu-Jun Guo; Zhen-Peng Gao; Chun-Feng Guo (Innovative Food Science & Emerging Technologies, 2025)

In/S co-decorated SnSe encapsulated in a dual carbon layer for sodium ion storage - Ya Ru Pei; Yong Jin Xia; Lei Ming Wang; Rui Li; Jun Xi Peng; Xue Jing Yang; Jian Li; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2025)

Nickel complex-bridging to enhance electron transport in covalent organic frameworks for efficient photocatalytic uranium reduction - Xiao-Xing Wang; Rui Zhang; Zhi-Hai Peng; Jing-Wen Gong; En-Min Hu; Cheng-Peng Niu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

The Mechanism of the Effect of FCC Slurry Oil Blending Ratio on the Colloidal Stability and Asphaltene Aggregation Behavior of Low-Sulfur Marine Fuel Oil - Aigang Li; Shengjun Guo; Jianwen Deng; Hong Chen; Jinxuan Wu; Ru Jiang; Jing Tan; Lihua Cheng; Libo Zhang; Qinzhen Fan (Journal of Marine Science and Engineering, 2025)
Addressing IMO 2020 compliance, this study investigates marine fuel oil production from hydrotreated residues, focusing on mitigating excessive total sediment potential (TSP) caused by over-hydrotreatment. This study systematically investigates the impact of blending ratios of Fluid Catalytic Cracking (FCC) slurry oil with Residue Desulfurization (RDS) heavy oil on TSP, colloidal stability, and asphaltene structure evolution. Techniques such as XRD, SEM, and XPS were employed to analyze the structural changes in asphaltenes during the TSP exceeding process. The results indicate that as the FCC slurry oil blending ratio increases, TSP in the blended oil initially rises and then decreases. The peak TSP value of 0.41% occurs at a 10% FCC slurry oil blending ratio, primarily due to high-saturation hydrocarbons in RDS heavy oil disrupting the colloidal stability of asphaltenes in FCC slurry oil. When the blending ratio reaches 25%, TSP significantly decreases to 0.09%, attributed to the solubilizing effect of high aromatic compounds in the FCC slurry oil on the asphaltenes. The ω(Asp)/ω(Res) ratio mirrors the TSP trend, and the colloidal solubilizing capacity of asphaltenes increases with the blending ratio. Asphaltenes in RDS heavy oil exhibit a spherical structure, whereas those in FCC slurry oil show a layered structure. The precipitated asphaltenes in the blends primarily result from the aggregation of asphaltenes in FCC slurry oil, with heteroatoms (N, S, O) mainly originating from RDS heavy oil asphaltenes. During the early stage of blending, TSP formation is dominated by FCC slurry oil asphaltenes, but increasing the aromatic content in the system can significantly reduce TSP. This work provides theoretical and technical support for optimizing marine fuel blending processes in petrochemical enterprises.

Molecular characterization and optical properties of methanol-soluble brown carbon chromophores in a metropolitan area of northeastern Asia - Yu-Chieh Ting; Yi-Ru Ko; Yueh-Ling Hung; Cheng-Hua Ma; Cheng-Chih Hsu; Yu-Hsiang Cheng (Science of The Total Environment, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Arabidopsis HSFA1b functions as a heat sensor inhibiting OST1-mediated stomatal closure through its adenylate-cyclase activity - Yu Zhang; Ru-Feng Song; Xiao-Yu Hu; Hui Zhou; Wei Wang; Junli Zhang; Xin Zhang; Liu-Mei Li; Su-Ting Wang; Yuwei Song; Fuyou Xiang; Jingjing Xing; et al. (Molecular Plant, 2025)

Integrating morphology, ecology, and genomics: Unraveling the population genetic and evolution within the Rosa graciliflora complex - Jia Miao; Liang-Ying Li; Zhen-Long Liang; Yu Feng; Cheng Zhang; Shi-Qi Li; Heng-Ning Deng; Jian Ru; Zhong-Yu Tang; Xin-Fen Gao (Molecular Phylogenetics and Evolution, 2025)

Waste to wealth: High-internal phase Pickering emulsions stabilized by defatted flaxseed particles were employed as a novel animal fat replacer in meat systems - Cheng-wei Ruan; Si-ying Huang; Jun-ru Qi; Qingrong Huang (Food Chemistry, 2025)

Corrigendum to “Characterization of γ-CD-MOF-stabilized thymol pickering emulsion films with enhanced preservation properties for Basa (Pangasius) fish” [Food Chemistry 476 (2025) 143273] - Yiyi Cheng; Xiaoguo Ying; Xuemei Cai; Yin Chen; Yan Xu; Ru Song; Haiyan Gao (Food Chemistry, 2025)

A programmed Ca2+ nanomodulator by dynamically regulating autophagy and neuroinflammation for Parkinson's disease therapy - Wengui Lu; Chuan Zhang; Yaru Zhang; Ru Xiao; Chaoqi Wei; Fan Zhang; Zhenbao Li; Hewan Xia; Mimi Wan; Zhifei Cheng; Qi Wang (Chemical Engineering Journal, 2025)

Overcoming the bottleneck in one-electron reduction of CO2 with mechanical energy-driven triboelectric plasma-enabled catalysis - Qinglong Ru; Bao Zhang; Sumin Li; Jiao Wang; Wei Jiang; Nannan Liu; Hui Hu; Yongcui Yang; Taifeng Liu; Qianhong Gao; Yifei Zhu; Yu Jia; et al. (Chemical Engineering Journal, 2025)

Endothelial Cell Integrin α6 Regulates Vascular Remodeling Through the PI3K/Akt-eNOS-VEGFA Axis After Stroke - Bing-Qiao Wang; Yang-Ying Duan; Mao Chen; Yu-Fan Ma; Ru Chen; Cheng Huang; Fei Gao; Rui Xu; Chun-Mei Duan (Neuroscience Bulletin, 2025)

Seismic risk and loss assessment models for highway continuous girder bridges in large-scale zones - Si-Qi Li; Peng-Fei Qin; Peng-Chi Chen; Yi-Ru Li; Jia-Cheng Han; Jian Zhong (Soil Dynamics and Earthquake Engineering, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Transcriptome-Wide Sequencing Identifies Non-Coding RNAs and Their Competing Endogenous RNA Networks During the Stages of pPGCLCs-Induced Differentiation - Zhan-Zhong Qiao; Qiu-Yuan Pang; Chang Xu; Xin-Lei Feng; Ming-Xin Zang; Ping Wang; Ying Zhang; Yong-Chao Liu; Qian-Ru Han; Wei Shen; Wei Ge; Shun-Feng Cheng (Stem Cell Reviews and Reports, 2025)

TISCalling: leveraging machine learning to identify translational initiation sites in plants and viruses - Ming-Ren Yen; Ya-Ru Li; Chia-Yi Cheng; Ting-Ying Wu; Ming-Jung Liu (Plant Molecular Biology, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Zirconium phosphate nanonetworks for enhanced soft tissue integration and antibacterial performance of zirconia implant abutments - Yingyue Sun; Qihong Zhang; Shuyi Wu; Kendrick Hii Ru Yie; Lei Cai; Yinyan Zhang; Wen Si; Huan Cheng; Zijian Zheng; Peng Gao; Jinsong Liu; Lei Lu (Chemical Engineering Journal, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

Characteristic noise of offshore wind turbine impacts the behavior and muscle physiology of sea cucumber Apostichopus japonicus - Xiaochen Cheng; Zhaoming Gao; Shuai Liu; Yongchao Hu; Wanyi Li; Libin Zhang; Xiaoshang Ru (Marine Pollution Bulletin, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

Floated Bi4Ti3O12@MoS2 p-n heterojunction anti-fouling hydrogels for efficient seawater purification - Ying Liu; Bingyan Ni; Ruotong Ru; Linlin Zhang; Hongfei Sun; Jianjun Liao; Cheng Li; Dexin Wang; Xiaodong Zhang; Wei Zhou (Journal of Environmental Chemical Engineering, 2025)

Characterization of γ-CD-MOF-stabilized thymol Pickering emulsion films with enhanced preservation properties for Basa (Pangasius) fish - Yiyi Cheng; Xiaoguo Ying; Xuemei Cai; Yin Chen; Yan Xu; Ru Song; Haiyan Gao (Food Chemistry, 2025)

Overcrowded steric engineering of through-space interactions for anti-quenching multi-resonance TADF materials - Ru-Jia Wang; Fan Zheng; Jie Hu; Yu-Lan Wu; Xiao-Long Liu; Jia-Xiong Chen; Longjiang Xing; Qiao-Er Wu; Yanping Huo; Wen-Cheng Chen (Chemical Engineering Journal, 2025)

Efficient catalyst-free CO2 reduction by CO2— radical anions at gas–liquid interface under ambient conditions - Nannan Liu; Qinglong Ru; Wei Jiang; Hui Hu; Yongcui Yang; Kailan Ma; Zuliang Du; Yu Jia; Xiaojing Yang; Bao Zhang; Gang Cheng (Chemical Engineering Journal, 2025)

Analysis of Wind–Wave Relationship in Taiwan Waters - Kai-Ho Cheng; Chih-Hsun Chang; Yi-Chung Yang; Yu-Hao Tseng; Chung-Ru Ho; Tai-Wen Hsu; Dong-Jiing Doong (Journal of Marine Science and Engineering, 2025)
The relationship between wind and waves has been extensively studied over time. However, understanding the local wind and wave relationship remains crucial for advancing renewable energy development and optimizing ocean management strategies. This study used wind and wave data collected by the ten weather buoys in the waters surrounding Taiwan to analyze regional sea states. The relationship between wind speed and significant wave height (SWH) was examined using regression analysis. Additionally, machine learning techniques were employed to assess the relative importance of features contributing to SWH growth. The regression analysis revealed that SWH in the waters surrounding Taiwan was not fully developed, with notable discrepancies observed between the waters east and west of Taiwan. According to the power law formula describing the relationship between wind speed and SWH, the eastern waters exhibited a larger prefactor coupled with a smaller scaling exponent, while the western waters manifested a converse parametric configuration. Through an evaluation of four machine learning algorithms, it was determined that wind speed is the most influential factor driving these regional differences, especially in the waters west of Taiwan. Beyond wind speed, air pressure or temperature emerged as the secondary feature factor governing wind–wave interactions in the waters east of Taiwan.

Poly (sodium acrylate-acrylamide) hydrogels for enrichment and purification of microalgal biomass in an open system: performance optimization and mechanistic analysis - Cong-Cong Tang; Yong-Qi Cheng; Sheng-Long Chen; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Journal of Environmental Management, 2025)

Enhancing color conversion of perovskite quantum dot-based micro-light-emitting diodes via electrochemical etching and flow chemistry system - Wen-Tse Huang; Yen-Huei Lin; Po-Yi Tu; Loan Thi Ngo; Wei-Cheng Chen; Kai-Ling Liang; Yen-Hsiang Fang; Chaochin Su; Ru-Shi Liu (Chemical Engineering Journal, 2025)

Quantitational life cycle assessment of Effluent-Energy-Carbon synergies and trade-offs in drinking water treatment plant upgrades - Yumeng Zhang; Zongqi Ding; Zewei Lin; Shoubin Chen; Shunjian Cheng; Kaiming Peng; Ru Guo; Xiangfeng Huang; Chen Cai; Jia Liu (Journal of Water Process Engineering, 2025)

Repeated measurements of urinary bisphenol A and its analogues in relation to sperm DNA damage - Yang-Juan Li; A-Xue Liu; Jia-Yue Zeng; Yu Miao; Min Zhang; Xiao-Ying Liu; Wu Yang; Ru-Cheng Li; Jin-Qin Zhu; Chang-Jiang Liu; Qiang Zeng (Journal of Hazardous Materials, 2025)

Structural and electronic regulation of transition metal borides: from controllable synthesis to industrial alkaline water splitting - Na Xu; Xin-Ru Li; Denghao Ouyang; Guodong Li; Shijian Cheng; Zhongmin Tang; Yong-Ming Chai; Bin Dong (Fuel, 2025)

A review on the genus Melodinus: traditional uses, phytochemical diversity and pharmacological activities of indole alkaloids - Si-Fan Teng; Fang-Ru Li; Qi-Min Cui; Afsar Khan; Ting He; Xiao-Dong Luo; Ya-Ping Liu; Gui-Guang Cheng (Phytochemistry Reviews, 2025)

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Microbiological, physicochemical, textural, and rheological properties of fermented soymilk produced with Enterococcus faecium and Lactiplantibacillus plantarum - Chang-Cheng Li; Shu-Jun Guo; Yu-Ting Feng; Yan-Ru Zhou; Yue Li; Zhen-Peng Gao; Chun-Feng Guo (Food Chemistry, 2025)

Is there an association between eye-level greenness and childhood hypertension using street view? Findings from the Seven Northeastern Cities study in China - Huang-Min Yang; Jing-Yao Wang; Cheng Li; Ya-Qin Zhang; Ruoyu Wang; Qi Yang; Yao Yao; Zilong Wang; Shu-Li Xu; He-Hai Huang; Qian-Sheng Hu; Ru-Qing Liu; et al. (Environmental Research, 2025)

Microplastic pollution in stony coral skeletons and tissues: A case study of accumulation and interrelationship in South Penghu Marine National Park, Taiwan Strait - Chih-Feng Chen; Yun-Ru Ju; Ming-Huang Wang; Yee Cheng Lim; Chiu-Wen Chen; Yu-Rong Cheng; Cheng-Di Dong (Journal of Hazardous Materials, 2025)

Origin and evolution of slope-confined canyons and their relationship with gas hydrate accumulation in the northwestern Qiongdongnan Basin, South China Sea - Zigui Chen; Tao Jiang; Wenzhao Sun; Yue Chen; Cong Cheng; Ru Yin (Geomorphology, 2025)

Effect of vacuum frying on the structure and bioactivity of proanthocyanidins in Chinese quince (Chaenomeles sinensis Koehne) fruit - Yu Lou; Xu Fang; Zi-Cheng Yang; Jia-Lin Fei; Yu-Ru Feng; Zhao Qin; Hua-Min Liu; Yu-Xiang Ma; Xue-De Wang (Food Chemistry, 2025)

Automatic and integrated detection of nucleic acid by using a dual-mode thermal controlled digital microfluidic chip - Jiaqi Liao; Chonghao Li; Jiajia Liu; Hao Cheng; Linmin Li; Guixi Tang; Ru Huang; Yating Lu; Siyue Chen; Qian Zhang; Hao Chen; Qinyuan Chen; et al. (Analytica Chimica Acta, 2025)

Estimating monthly NO2, O3, and SO2 concentrations via an ensemble three-stage procedure with downscaled satellite remote sensing data and ground measurements - Chu-Chih Chen; Yin-Ru Wang; Fu-Cheng Wang; Yi-Shiang Shiu; Chang-Fu Wu; Tang-Huang Lin (Journal of Hazardous Materials, 2024)

Developing novel microwave-assisted induction heating (MAIH) technology for heating in-packaged ready-to-eat chicken breast products - Chiu-Chu Hwang; Yu-Ru Huang; Cheng-Da Hsieh; Yi-Chen Lee (Innovative Food Science & Emerging Technologies, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

A review of urinary HPV testing for cervical cancer management and HPV vaccine surveillance: rationale, strategies, and limitations - Lin Cheng; Ru Wang; Jing Yan (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Emergency control of dinoflagellate bloom in freshwater with chlorine enhanced by solar radiation: Efficiency and mechanism - Ru Wang; Ya Cheng; Qiqi Wan; Ruihua Cao; Jie Cai; Tinglin Huang; Gang Wen (Water Research, 2024)

Experimental study on the influence of particle morphology on compression characteristics of coral sand in South China Sea - Ru Qu; Cheng-hao Ma; Chang-qi Zhu; Hai-feng Liu (Ocean Engineering, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Single and mixture toxicity of benzophenone-3 and its metabolites on Daphnia magna - Yun-Ru Ju; Chang-Rui Su; Chih-Feng Chen; Cheng-Fu Shih; Li-Siang Gu (Chemosphere, 2024)

Most appropriate nozzle of six-rotor UAV for prescribed spraying liquid in tea plantation under effects of downwash flow structure in hover - Nai-Hong Hu; Wen-Xuan Zhou; Lin Zhu; Yan-Cheng Li; Xin-Yu Xie; Ru-Yan Hou; Cheng-Long Yin (Crop Protection, 2024)

Ubiquity and ecological risks of conjugated steroids cannot be overlooked: First evidence from estuarine sediments - Fei Tian; Shan Liu; Ru Xu; Nian-Nian Wu; Shuang-Shuang Liu; Yuan-Yue Cheng; Qian Xiong; Zhen-Zhao Tang; Lin-Bao Zhang; Zhe Zhang; Hai-Gang Chen (Marine Pollution Bulletin, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Technology-driven carbon-neutral pathway analysis for Urban Wastewater Treatment Plants - Haoran Wu; Chen Cai; Lian Yu; Zhenxing Shang; Yumeng Zhang; Xiaojing Ni; Ru Guo; Jia Liu; Kaiming Peng; Xiangfeng Huang; Limin Zhang; Zhaochang Huang; et al. (Journal of Cleaner Production, 2024)

Bi2O3/Bi@CSs achieved by shock-type heating for fast and long-lasting sodium ion battery - Ya Ru Pei; Xue Jing Yang; Wu Bin Wan; Hai Ming Huang; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2024)

Enhancing osseointegration and angiogenesis of Titanium implants through KMnO4-Modified Montmorillonite nano-clay coating - Lifeng Xiong; Binwei Dai; Baodi Yin; Kendrick Hii Ru Yie; Haobo Sun; Yang Liu; Zheyuan Liu; Ahmed S. Mahany; Huan Cheng; Lihua Xu; Peng Gao; Lei Lu; et al. (Chemical Engineering Journal, 2024)

Improved prediction of swimming talent through random forest analysis of anthropometric and physiological phenotypes - Cheng Liu; Bingxiang Xu; Kang Wan; Qin Sun; Ruwen Wang; Yue Feng; Hui Shao; Tiemin Liu; Ru Wang (Phenomics, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Characteristics Analysis of Acoustic Doppler Current Profile Measurements in Northeast Taiwan Offshore - Chung-Ru Ho; Kai-Ho Cheng; Zhe-Wen Zheng; Hung-Jen Lee; Tai-Wen Hsu (Journal of Marine Science and Engineering, 2024)
A comprehensive study was conducted at a wave energy device test site located off the northeastern coast of Taiwan to assess the influence of oceanic currents on experimental equipment. A bottom-mounted 600 kHz acoustic Doppler current profiler, equipped with integrated temperature and pressure sensors, was deployed at a depth of approximately 31 m. This study, spanning from 6 June 2023 to 11 May 2024, recorded ocean current profiles by assembling data from 50 pings every 10 min, with a resolution of one meter per depth layer. The findings reveal that variations in water levels were predominantly influenced by the M2 tidal constituent, followed by the O1, K1, and S2 tides. Notably, seawater temperature fluctuations at the seabed were modulated by tides, especially the M2 tide. A significant drop in seawater temperature was also observed as the typhoon passed through the south of Taiwan. In terms of sea surface currents, the measured maximum current speed was 71.89 cm s−1, but the average current speed was only 15.47 cm s−1. Tidal currents indicated that the M4 and M2 tides were the most significant, with semimajor axes and inclination angles of 8.48 cm s−1 and 102.60°, and 7.00 cm s−1 and 97.76°, respectively. Seasonally, barotropic tidal currents were the strongest in winter. Additionally, internal tides were identified, with the first baroclinic mode being dominant. The zero-crossing depths varied between 14 and 18 m. During the summer, the M2 baroclinic tidal current displayed characteristics of the second baroclinic mode, with zero-crossing depths at approximately 7 m and 22 m. This node aligns with results from the empirical orthogonal function analysis and correlates with the depths’ significant shifts in seawater temperature as measured by a conductivity, temperature, and depth instrument. Despite the velocities of internal tides not being strong, the directional variance between surface and bottom flows presents critical considerations for the deployment and operation of moored wave energy devices.

Applications in Pickering emulsions of enhancing preservation properties: Current trends and future prospects in active food packaging coatings and films - Yiyi Cheng; Xuemei Cai; Xin Zhang; Yadong Zhao; Ru Song; Yan Xu; Haiyan Gao (Trends in Food Science & Technology, 2024)

Biofunctionalized hydrogel composed of genipin-crosslinked gelatin/hyaluronic acid incorporated with lyophilized platelet-rich fibrin for segmental bone defect repair - Er-Yuan Chuang; Yi-Cheng Lin; Yu-Min Huang; Chih-Hwa Chen; Yi-Yen Yeh; Lekha Rethi; Yu-Jen Chou; Pei-Ru Jheng; Jen-Ming Lai; Chang-Jung Chiang; Chin-Chean Wong (Carbohydrate Polymers, 2024)

Combining satellite data and artificial intelligence with a crop growth model to enhance rice yield estimation and crop management practices - Nguyen-Thanh Son; Chi-Farn Chen; Youg-Sin Cheng; Cheng-Ru Chen; Chien-Hui Syu; Yi-Ting Zhang; Shu-Ling Chen; Shih-Hsiang Chen (Applied Geomatics, 2024)

Accurate and precise in situ determination of beryllium contents in beryllium minerals using ablation spot size of 13 μm by LA–ICP–MS - Wen-Kai Jin; Xu-Dong Che; Ru-Cheng Wang; Huan Hu; Can Rao; Wen-Lan Zhang; Xiao-Feng Li (Journal of Geochemical Exploration, 2024)

Assessing spatial heterogeneity of nutrient loads in a large shallow lake using a lattice Boltzmann water quality model - Haifei Liu; Chuqi Zhang; Wei Yang; Zhiming Ru; Jiewei Ding; Yuetong Jing; Cheng Li (Journal of Environmental Management, 2024)

Estimation of linezolid exposure in patients with hepatic impairment using machine learning based on a population pharmacokinetic model - Ru Liao; Lihong Chen; Xiaoliang Cheng; Houli Li; Taotao Wang; Yalin Dong; Haiyan Dong (European Journal of Clinical Pharmacology, 2024)

Numerical modeling on wave–current flows and bed shear stresses over an algal reef - Yi-Ru Lan; Zhi-Cheng Huang (Environmental Fluid Mechanics, 2024)
Currents in coastal zones under multiple mechanisms in terms of tides, waves, wind, and high roughness are difficult to model; bed shear stresses under wave–current flows are particularly challenging yet not being well studied. Few studies reported the modeling and validation of the bed shear stress in reef environments. In this paper, we present the first direct assessment of numerical modeling on depth-averaged currents and bed shear stresses over an algal reef using a coupled wave–current model (Delft-3D). The modeled results were validated and compared to the field observed data. The model considers hydrodynamic forcing in terms of tides, waves, wind stresses, and bed friction. Results show that the model generally reproduces the depth-averaged currents and bed shear stresses when considering all the mechanisms. Two numerical cases with and without wind forcing were tested to examine the effects of the winds. We found that the tide is mostly the primary factor driving the current, even in shallow waters within a depth of 3 m; however, the currents are also significantly affected by wind speeds and wind directions during high-wind events. When the wind direction is in the same direction as the tidal current, the current speed increases, suggesting the importance of the wind stress on the coastal currents. In addition, two models were chosen to study the nonlinear enhancement of bed shear stress by waves. We found a significant difference between the two models in predicting the bed shear stresses compared to the observed data. Nonlinear contribution from wave enhances the magnitude of bed shear stresses, which reduces the model error. The results highlight the nonlinear interaction between waves and currents is meaningful in predicting the bed shear stresses during high-wave-orbital motions; improvement of the present wave-current nonlinear interaction model for predicting the bed shear stresses may be needed.

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Asperidulins A and B, two new prenylxanthone derivatives from an apple-derived fungus Aspergillus nidulans KIB-HACM-01 - Peng Lai; Li Wang; Chenjie Deng; Yixin Xu; Xiao-Yan Ma; Chun-Ru Cheng; Sheng-Xiong Huang (Natural Product Research, 2024)

Distance-decay equations of antibiotic resistance genes across freshwater reservoirs - Zhao-Feng Guo; Kiranmoy Das; Wiebke J. Boeing; Yao-Yang Xu; Edoardo Borgomeo; Dong Zhang; Si-Cheng Ao; Xiao-Ru Yang (Water Research, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Exploring efficient copper recovery and recycling in Taiwan's printed circuit board manufacturing through material-flow cost accounting - Fang-Ru Chou; Remi Chauvy; Pi-Cheng Chen (Sustainable Production and Consumption, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Cysteine and glycine-rich protein 2 is crucial for maintaining the malignant phenotypes of gliomas through its action on Notch signalling cascade - Lingtong Liu; Fei Li; Lingxue Zhang; Yingying Cheng; Lin Wu; Ru Tie; Xiaobing Jiang; Wenwen Gao; Bochuan Liu; Yao Wei; Pan Chang; Jun Xu; et al. (Toxicology and Applied Pharmacology, 2024)

Urinary haloacetic acid concentrations and thyroid function among women: Results from the TREE study - Yang Wu; Yan-Ling Deng; Min Zhang; Yu Miao; Fei-Peng Cui; Jia-Yue Zeng; Xiao-Ying Liu; Cheng-Ru Li; A-Xue Liu; Jin-Qin Zhu; Yang-Juan Li; Chong Liu; et al. (Science of The Total Environment, 2024)

Differences among Lactiplantibacillus plantarum strains isolated from different fermented foods in their potential cholesterol-lowering properties - Shu-Jun Guo; Chang-Cheng Li; Yu-Ting Feng; Yan-Ru Zhou; Bin Liu; Zhen-Peng Gao; Chun-Feng Guo (Food Bioscience, 2024)

A freestanding rotating triboelectric nanogenerator with large area and high efficiency for triboelectric plasma CO2 reduction - Hongjie Cao; Qinglong Ru; Dongyang Fang; Sumin Li; Nannan Liu; Wei Jiang; Hui Hu; Yongcui Yang; Guangqin Gu; Bao Zhang; Gang Cheng; Sanjun Yang; et al. (Chemical Engineering Journal, 2024)

Multi-omics analysis reveals mechanism of Schisandra chinensis lignans and acteoside on EMT in hepatoma cells via ERK1/2 pathway - Jingjing Jiang; Ru Cheng; Aoqi Song; Yuefen Lou; Guorong Fan (Functional & Integrative Genomics, 2024)

Panax quinquefolius saponins and panax notoginseng saponins attenuate myocardial hypoxia-reoxygenation injury by reducing excessive mitophagy - Junyan Xia; Cong Chen; Yanan Sun; Sinai Li; Yuxuan Li; Bai-Ru Cheng; Yanting Pang; Yan Li; Dong Li; Qian Lin (Cell Biochemistry and Biophysics, 2024)

Identification of a Clinical Spirometra mansoni Plerocercoid Isolate Using Molecular and Morphological Data - Si Si Ru; Chi Cheng; Peng Jiang; Xi Zhang (Acta Parasitologica, 2024)

Potential roles of hydroxybenzoate paralytic shellfish toxins in modulating toxin biokinetics in scallops - Zhuo-Ru Lin; Hui-Xia Geng; Ren-Cheng Yu (Journal of Hazardous Materials, 2024)

Direct and indirect monitoring methods for nitrous oxide emissions in full-scale wastewater treatment plants: A critical review - Zhenxin Shang; Chen Cai; Yanli Guo; Xiangfeng Huang; Kaiming Peng; Ru Guo; Zhongqing Wei; Chenyuan Wu; Shunjian Cheng; Youxiang Liao; Chih-Yu Hung; Jia Liu (Journal of Environmental Management, 2024)

Phosphorylated covalent organic framework/graphene composites for photoelectrothermal integrated collaborative reduction of uranium - Rui Zhang; Liang Tao; Cheng-Peng Niu; Cheng-Rong Zhang; Tie-Ying Shi; Xiao-Xing Wang; Ying-Ao Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Time-dependent nonmonotonic concentration-response and synergism of alkyl glycosides with different alkyl side chain to Vibrio qinghaiensis sp. -Q67 - Meng-Ting Tao; Shu-Shen Liu; Ting-Ting Ding; Zhong-Wei Gu; Ru-Jun Cheng (Science of The Total Environment, 2024)

Insights into the response of nitrogen metabolism to sulfamethoxazole contamination in constructed wetlands with varied substrates - Ya-Ru Zhang; Jia-Min Xu; Hao-Ran Xu; Guo-Dong Zhang; Xian-Bin Liu; Hao-Yi Cheng (Bioresource Technology, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Seismic hazard models for typical urban masonry structures considering optimized regression algorithms - Si-Qi Li; Yi-Ru Li; Jia-Cheng Han; Peng-Fei Qin; Ke Du (Bulletin of Earthquake Engineering, 2024)

Migration of phosphorus in pig manure during pyrolysis process and slow-release mechanism of biochar in hydroponic application - Ru-Qing Jiang; Guang-Wei Yu; Lin-Hui Yu; Yu Wang; Chang-Jiang Li; Zhen-Jiao Xing; Xi-Mei Xue; Yin Wang; Cheng Yu (Science of The Total Environment, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Exposures to drinking water disinfection byproducts and kidney function in Chinese women - Cheng-Ru Li; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Chong Liu; Qiang Zeng (Environmental Research, 2024)

Unravelling hidden threats of water disinfection: Toxicity evaluation and toxic products identification during diclofenac degradation - Ding Pan; Cheng Zhang; Cai-Shan Wang; Peng Zhang; Xin-Yi Jiao; Qian-Ru Ma; Li-Ting Wang; Dai-Jun Li; Li-Ping Li (Environmental Pollution, 2024)

Formation of lithium-rich pegmatites via rapid crystallization and shearing – case study from the South Tibetan Detachment, Himalaya - Xiao-Chi Liu; Matthew J. Kohn; Jia-Min Wang; Shao-Xiong He; Ru-Cheng Wang; Fu-Yuan Wu (Earth and Planetary Science Letters, 2024)

Inflammation and Brain Structure in Alzheimer’s Disease and Other Neurodegenerative Disorders: a Mendelian Randomization Study - Wei-Shi Liu; Ya-Ru Zhang; Yi-Jun Ge; Hui-Fu Wang; Wei Cheng; Jin-Tai Yu (Molecular Neurobiology, 2024)

Urinary biomarkers of drinking-water disinfection byproducts in relation to diminished ovarian reserve risk: A case-control study from the TREE cohort - Xiao-Ying Liu; Min Zhang; Xiao-Li Gu; Yan-Ling Deng; Chong Liu; Yu Miao; Yang Wu; Cheng-Ru Li; Jia-Yue Zeng; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; et al. (Science of The Total Environment, 2024)

Natural products from the culture broth of an actinobacteria Streptomyces sp. M5205 and evaluation of their antifungal activity - Jih-Jung Chen; Ming-Jen Cheng; Min Tseng; Ming-Der Wu; Jing-Ru Weng (Phytochemistry Letters, 2024)

ABA functions in low phosphate-induced anthocyanin accumulation through the transcription factor ABI5 in Arabidopsis - Ru-Feng Song; Xiao-Yu Hu; Wen-Cheng Liu; Hong-Mei Yuan (Plant Cell Reports, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Assessing production–living–ecological spaces and its urban–rural gradients in Xiangyang City, China: insights from land-use function symbiosis - Chao Liu; Qingke Yang; Fenghua Zhou; Ru Ai; Long Cheng (Environmental Science and Pollution Research, 2024)

Peduncle collision-free grasping based on deep reinforcement learning for tomato harvesting robot - Yajun Li; Qingchun Feng; Yifan Zhang; Chuanlang Peng; Yuhang Ma; Cheng Liu; Mengfei Ru; Jiahui Sun; Chunjiang Zhao (Computers and Electronics in Agriculture, 2024)

Transcriptomic analysis reveals the immune response mechanisms of sea cucumber Apostichopus japonicus under noise stress from offshore wind turbine - Xiaochen Cheng; Libin Zhang; Zhaoming Gao; Kehan Li; Jialei Xu; Weijian Liu; Xiaoshang Ru (Science of The Total Environment, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

Associations between urinary biomarkers of exposure to disinfection byproducts and semen parameters: A repeated measures analysis - Min Zhang; Xiao-Ying Liu; Yan-Ling Deng; Chong Liu; Jia-Yue Zeng; Yu Miao; Yang Wu; Cheng-Ru Li; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Qiang Zeng (Journal of Hazardous Materials, 2024)

Fully space-confined donor-acceptor interaction for highly efficient thermally activated delayed fluorescence emitters - Wen-Cheng Chen; Ming-Hui Zheng; Yu-Lan Wu; Ru-Jia Wang; Jia-Ming Jin; Si-Wei Chen; Bo Liu; Jia-Xiong Chen; Yanping Huo; Shaomin Ji (Chemical Engineering Journal, 2024)

A Dual Functional Fluorescent Probe Based on Phenothiazine for Detecting Hg2+ and ClO− and its Applications - Cheng-lu Zhang; Chang Liu; Shi-ru Nie; Yang Zhang; Jing-hao Guo; Xiang-ling Li; Cui Liu (Journal of Fluorescence, 2023)

Clarification of the phosphorus release mechanism for recovering phosphorus from biofilm sludge in alternating aerobic/anaerobic biofilm system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yang Pan; Lin Chen; Liang Zhu; Yi-Ping Li; Jing-Ru Li (Science of The Total Environment, 2023)

Magmatic–hydrothermal evolution of the Koktokay No. 3 pegmatite, Altai, northwestern China: Constraints from in situ boron isotope and chemical compositions of tourmaline - Rong Yin; Xiao-Long Huang; Ru-Cheng Wang; Gang-Jian Wei; Yi-Gang Xu; Yu Wang; Xiao-Ming Sun; Le Zhang; Xiao-Ping Xia (Lithos, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Wood frame structured carbons with integrated sieving layer for propylene/propane separation - Cheng-Tong Wang; Wen-Cui Li; Shuang Xu; Ru-Shuai Liu; Guang-Ping Hao; An-Hui Lu (Chemical Engineering Journal, 2023)

Microplastics in coral reef sediments underestimated? They may hide in biominerals - Chih-Feng Chen; Yun-Ru Ju; Chiu-Wen Chen; Frank Paolo Jay B. Albarico; Yee Cheng Lim; Chongtai Ke; Yu-Rong Cheng; Cheng-Di Dong (Science of The Total Environment, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

Dual N-modification enables high-performance Solid-State Li metal batteries with Li5.5PS4.5Cl1.5 - Chaochao Wei; Ru Wang; Zhongkai Wu; Qiyue Luo; Ziling Jiang; Liang Ming; Long Zhang; Hongcheng Lu; Guangshe Li; Liping Li; Chuang Yu; Shijie Cheng (Chemical Engineering Journal, 2023)

Mechanical energy-driven triboelectric plasma catalytic CO2 reduction over oxygen-vacancy-introduced In2O3 nanoparticles - Xiaochen Xiang; Jiao Wang; Qinglong Ru; Sumin Li; Ke Zhao; Yifei Zhu; Zhenpan Chen; Liangliang Liu; Guangqin Gu; Yu Jia; Bao Zhang; Gang Cheng; et al. (Chemical Engineering Journal, 2023)

Efficient removal of uranium under strong acid based on charge separation and protonation coupled covalent organic frameworks - Shun-Mo Yi; Cheng-Rong Zhang; Xin Liu; Xiao-Juan Chen; Jia-Xin Qi; Cheng-Peng Niu; Jin-Lan Liu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

YOLACTFusion: An instance segmentation method for RGB-NIR multimodal image fusion based on an attention mechanism - Cheng Liu; Qingchun Feng; Yuhuan Sun; Yajun Li; Mengfei Ru; Lijia Xu (Computers and Electronics in Agriculture, 2023)

Microplastics in coastal farmed oyster (Crassostrea angulata) shells: Abundance, characteristics, and diversity - Chih-Feng Chen; Yun-Ru Ju; Yee Cheng Lim; Ming-Huang Wang; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Targeting STING-mediated pro-inflammatory and pro-fibrotic effects of alveolar macrophages and fibroblasts blunts silicosis caused by silica particles - Liang Ou; Peng Zhang; Zhengpeng Huang; Yuxing Cheng; Qianru Miao; Ru Niu; Yuxin Hu; Ying Chen (Journal of Hazardous Materials, 2023)

Probing the national development from heavy metals contamination in river sediments - Xianghong Guan; Xuan Ru; Guanglei Qiu; Zemin Li; Xiaoqian Cheng; Xiong Ke; Acong Chen; Chaohai Wei (Journal of Cleaner Production, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Partially miscible droplet microfluidics to enhance interfacial adsorption of hydrophilic nanoparticles for colloidosome synthesis - Wei-Yi Chu; Yi-Ru Chiou; Ren-Hao Luo; Tzu-Heng Chen; Cheng-Ju Yu; Yi-Ju Chou; Huan-Tsung Chang; Chien-Fu Chen (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Comprehensive assessment of metals and organic pollutants in pelagic fishing port sediments - Chih-Feng Chen; Shu-Hui Lee; Yun-Ru Ju; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Variations of methane fluxes and methane microbial community composition with soil depth in the riparian buffer zone of a sponge city park - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Liangqian Fan; Wei Chen; Lin Cheng; et al. (Journal of Environmental Management, 2023)

Effect of liver metastasis on the efficacy of immune checkpoint inhibitors in cancer patients: a systemic review and meta-analysis - Bao-Wen Tian; Cheng-Long Han; Han-Chao Wang; Lun-Jie Yan; Zi-Niu Ding; Hui Liu; Xin-Cheng Mao; Jin-Cheng Tian; Jun-Shuai Xue; Long-Shan Yang; Si-Yu Tan; Zhao-Ru Dong; et al. (Clinical & Experimental Metastasis, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Nonagricultural emissions enhance dimethylamine and modulate urban atmospheric nucleation - Yunhua Chang; Qingyang Ling; Xinlei Ge; Xiangyang Yuan; Shengqian Zhou; Kai Cheng; Jianjiong Mao; Dandan Huang; Qingyao Hu; Jun Lu; Shijie Cui; Yaqing Gao; et al. (Science Bulletin, 2023)

Anti-inflammatory lanostane triterpenoids with rearranged spirobi[indene] scaffold and their biogenetically related analogues from Euphorbia maculata - Ru-Feng Xia; Jun-Cheng Su; Jun Yu; Hong-Jing Zha; Jia-Le Wu; Xiao-Na Fu; Qin Cai; Luo-Sheng Wan (Phytochemistry, 2023)

Highly sensitive plasmonic biosensor for hepatitis B virus DNA based on the surface etching of the active helical gold nanorods - Ru Cheng; Liang Tong Li; Min Huang; Fu Zhu; Qian Li; Hui Liu; Jie Gao; Xiao Hui Zhao; Fu Kang Luo; Jian Wang (Chemical Engineering Journal, 2023)

Ganglioside-focused Glycan Array Reveals Abnormal Anti-GD1b Auto-antibody in Plasma of Preclinical Huntington’s Disease - Tien-Wei Lin; Jung-Kai Chang; Yih-Ru Wu; Tsung-Hsien Sun; Yang-Yu Cheng; Chien-Tai Ren; Mei-Hung Pan; Jin-Lin Wu; Kuo-Hsuan Chang; Hwai-I Yang; Chiung-Mei Chen; Chung-Yi Wu; et al. (Molecular Neurobiology, 2023)

Exosomal MiR-381 from M2-polarized macrophages attenuates urethral fibroblasts activation through YAP/GLS1-regulated glutaminolysis - Ye-Hui Chen; Yi-Cheng Xu; Ting-Ting Lin; Hang Chen; Ru-Nan Dong; Feng-Ping Cai; Zhi-Bin Ke; Jia-Yin Chen; Yong Wei; Qing-Shui Zheng; Xue-Yi Xue; Ning Xu (Inflammation Research, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Environmental regulation, industrial agglomeration, and marine green development efficiency: an empirical analysis from China’s coastal provinces - Ke-Liang Wang; Xiang-Xiang Ru; Li-Li Ding; Yun-He Cheng (Environmental Science and Pollution Research, 2023)

A novel pollution index to assess the metal bioavailability and ecological risks in sediments - Chih-Feng Chen; Yee Cheng Lim; Yun-Ru Ju; Frank Paolo Jay B. Albarico; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

Dispersive adsorption and anticorrosion properties of natural capsaicin on Q235 steel in mixed H2SO4 and NaCl environment: Characterization, experimental and theoretical studies - Wilfred Emori; Hitler Louis; Paul C. Okonkwo; Demian I. Njoku; Henry O. Edet; Peter C. Okafor; Chun-Ru Cheng (Sustainable Chemistry and Pharmacy, 2023)

An extended SW-TES algorithm for land surface temperature and emissivity retrieval from ECOSTRESS thermal infrared data over urban areas - Chen Ru; Si-Bo Duan; Xiao-Guang Jiang; Zhao-Liang Li; Cheng Huang; Meng Liu (Remote Sensing of Environment, 2023)

Electrochemical etching induced high-valence cobalt with defects site for boosting electrochemical water splitting - Hongmei Gao; Jiaqi Liu; Zijin Zhang; Yuxuan Lu; Ru Chen; Yu-Cheng Huang; Chao Xie; Mengyi Qiu; Tianyu Wu; Jinbo Wang; Yubin Jiang; Chung-Li Dong; et al. (Chemical Engineering Journal, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Circulating polyunsaturated fatty acids, fish oil supplementation, and risk of incident dementia: a prospective cohort study of 440,750 participants - Yu He; Shu-Yi Huang; Hui-Fu Wang; Wei Zhang; Yue-Ting Deng; Ya-Ru Zhang; Qiang Dong; Jian-Feng Feng; Wei Cheng; Jin-Tai Yu (GeroScience, 2023)

mRNA 3ʹ -UTR-mediate translational control through PAS and CPE in sheep oocyte - Chun-Ru Song; Ru-Jing Zhang; Fang-Rui Xue; Xiao-Jie Zhang; Xing-Yue Wang; Dui Sun; Kang Ding; Qi Yang; Xin-Yu Wang; Cheng-Guang Liang (Theriogenology, 2023)

Flexible three-dimensional covalent organic frameworks for ultra-fast and selective extraction of uranium via hydrophilic engineering - Xiao-Juan Chen; Cheng-Rong Zhang; Xin Liu; Jia-Xin Qi; Wei Jiang; Shun-Mo Yi; Cheng-Peng Niu; Yuan-Jun Cai; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Extraction of weak hydrophobic sulforaphane from broccoli by salting-out assisted hydrophobic deep eutectic solvent extraction - Wen-wen Deng; Xue-ping Mei; Zi-jun Cheng; Tian-xiang gan; Xuan Tian; Jiang-nan Hu; Chuan-ru Zang; Bo Sun; Jing Wu; Yin Deng; Reza. A. Ghiladi; George H. Lorimer; et al. (Food Chemistry, 2023)

Self-oxidation cycle of oxidized red phosphorus for regeneration of binding sites enables efficient uranium extraction in tributylphosphate-kerosene system - Yingtong Lv; Ru Cheng; Guolin Yang; Wang Liu; Jingye Zhang; Xiaofang Yu; Wencai Bai; Rong He; Wenkun Zhu (Chemical Engineering Journal, 2023)

SnS2-covalent organic framework Z-scheme van der Waals heterojunction for enhanced photocatalytic reduction of uranium (VI) in rare earth tailings wastewater - Xin Liu; Rui-Xiang Bi; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Whole exome sequencing improves genetic diagnosis of fetal clubfoot - Ruibin Huang; Hang Zhou; Chunling Ma; Fang Fu; Ken Cheng; You Wang; Ru Li; Tingying Lei; Qiuxia Yu; Dan Wang; Shujuan Yan; Xin Yang; et al. (Human Genetics, 2023)

Restrictions on Niobium enrichment by alteration of Niobium-rich biotite in pure water, acid, alkaline and fluoride-bearing solutions at 200 MPa and 300–600 °C - Zhao-Yu Yang; Ru-Cheng Wang; Xu-Dong Che; Daniel Harlov (Geochimica et Cosmochimica Acta, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

The immunostimulatory effects of Theobroma cacao L. pod husk extract via injection and dietary administrations on Macrobrachium rosenbergii and its resistance against Lactococcus garvieae - Hsin-Wei Kuo; Cheng-Ying Li; Yun-Ru Chen; Winton Cheng (Fish & Shellfish Immunology, 2023)

Synthesis and evaluation of phase change material suitable for energy-saving and carbon reduction of building envelopes - Ru Ji; Xiang Li; Cheng Lv (Energy and Buildings, 2023)

Dissolved organic matter–assisted phytoremediation potential of cotton for Cd-contaminated soil: a relationship between dosage and phytoremediation efficiency - Tao Min; Tong Luo; Hao He; Jie Qin; Yan Wang; Liyang Cheng; Sibo Ru; Junhua Li (Environmental Science and Pollution Research, 2022)

Acute Toxicity of a Novel anti-fouling Material Additive DCOIT to Marine Chlorella sp - Jin-Chuang Ru; Xue-Li Zhao; Zhi-Han Cao; Cheng-Zhuang Chen; Ping Li; Zhi-Hua Li (Bulletin of Environmental Contamination and Toxicology, 2022)

Damage and Failure Characteristics and Constitutive Model of Copper-Bearing Skarns Disturbed by Hierarchical Dynamic Loading After Loading And Unloading - Chun Wang; Jia Li; Lu- ping Cheng; Xin-ru Li; Pan-long Zhang; Man-gu Hu (Rock Mechanics and Rock Engineering, 2022)

Insights into the development of pentylenetetrazole-induced epileptic seizures from dynamic metabolomic changes - Xue Zhao; Peixuan Cheng; Ru Xu; Kaili Meng; Sha Liao; Pu Jia; Xiaohui Zheng; Chaoni Xiao (Metabolic Brain Disease, 2022)

Traffic noise and adiposity: a systematic review and meta-analysis of epidemiological studies - Si-Yu Gui; Ke-Jia Wu; Yue Sun; Yue-Nan Chen; Huan-Ru Liang; Wen Liu; Yao Lu; Cheng-Yang Hu (Environmental Science and Pollution Research, 2022)

High Levels of 25-OH-Vitamin D and Copper in Pregnant Women with Abnormal Glucose Challenge Test - Chien-Hua Chiang; Wan-Ju Kung; Chien-Hung Lee; Yeong-Hwa Zen; Cheng-Fa Lee; Hui-Ru Yang; Ching-Chiang Lin; Yeou-Lih Huang (Biological Trace Element Research, 2022)

Detection of bloom-forming dinoflagellates Karenia mikimotoi and Prorocentrum donghaiense using qPCR assays - Xiao-Kun Hu; Zhuo-Ru Lin; Qing-Chun Zhang; Fan-Zhou Kong; Jing-Yi Cen; Yu-Lan Zeng; Ren-Cheng Yu (Journal of Applied Phycology, 2022)

Exploiting Sentinel-1 data and machine learning–based random forest for collectively mapping rice fields in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Youg-Sin Cheng; Piero Toscano; Chein-Hui Syu; Horng-Yuh Guo; Shu-Ling Chen; Tsang-Sen Liu; Yi-Ting Zhang; Huan-Sheng Lin; Shih-Hsiang Chen; et al. (Applied Geomatics, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Vibrational Characterization and Molecular Electronic Investigations of 2-acetyl-5-methylfuran using FT-IR, FT-Raman, UV–VIS, NMR, and DFT Methods - Victoria M. Bassey; Chioma G. Apebende; Precious S. Idante; Hitler Louis; Wilfred Emori; Chun-Ru Cheng; John A. Agwupuye; Tomsmith O. Unimuke; Kun Wei; Fredrick C. Asogwa (Journal of Fluorescence, 2022)

Imatinib-induced hepatotoxicity via oxidative stress and activation of NLRP3 inflammasome: an in vitro and in vivo study - Feng-Ru Huang; Wen-Tong Fang; Zi-Ping Cheng; Ye Shen; Dun-Jian Wang; Yong-Qing Wang; Lu-Ning Sun (Archives of Toxicology, 2022)

Synthesis and biological activity of amide derivatives derived from natural product Waltherione F - Hongbin Fang; Zhanfang Chen; Xuewen Hua; Wenrui Liu; Chenmeng Xue; Yi Liu; Xiaohe Zhu; Man Yuan; Shuang Cheng; Bingxiang Wang; Jing Ru; Dzmitry Bazhanau; et al. (Medicinal Chemistry Research, 2022)

Haloterrigena gelatinilytica sp. nov., a new extremely halophilic archaeon isolated from salt-lake - Bing-Bing Liu; Nimaichand Salam; Manik Prabhu Narsing Rao; Shuang Cheng; Yuan-Guo Xie; Lai-You Wang; Yuan-ru Zhang; Xin-Yuan Yu; Shu-xian Guo; Wen-Jun Li (Archives of Microbiology, 2022)

circSVIL regulates bovine myoblast development by inhibiting STAT1 phosphorylation - Binglin Yue; Haiyan Yang; Jiyao Wu; Jian Wang; Wenxiu Ru; Jie Cheng; Yongzheng Huang; Xianyong Lan; Chuzhao Lei; Hong Chen (Science China Life Sciences, 2022)

Household environmental microbiota influences early‐life eczema development - Le Duc Huy Ta; Carina Jing Xuan Tay; Christophe Lay; Paola Florez de Sessions; Cheryl Pei Ting Tan; Michelle Jia Yu Tay; Hui Xing Lau; Atiqa Binte Zulkifli; Gaik Chin Yap; Elizabeth Huiwen Tham; Eliza Xin Pei Ho; Anne Eng Neo Goh; et al. (Environmental Microbiology, 2021)
Summary Exposure to a diverse microbial environment during pregnancy and early postnatal period is important in determining predisposition towards allergy. However, the effect of environmental microbiota exposure during preconception, pregnancy and postnatal life on development of allergy in the child has not been investigated so far. In the S‐PRESTO (Singapore PREconception Study of long Term maternal and child Outcomes) cohort, we collected house dust during all three critical window periods and analysed microbial composition using 16S rRNA gene sequencing. At 6 and 18 months, the child was assessed for eczema by clinicians. In the eczema group, household environmental microbiota was characterized by presence of human‐associated bacteria Actinomyces , Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium at all time points, suggesting their possible contributions to regulating host immunity and increasing the susceptibility to eczema. In the home environment of the control group, putative protective effect of an environmental microbe Planomicrobium ( Planococcaceae family) was observed to be significantly higher than that in the eczema group. Network correlation analysis demonstrated inverse relationships between beneficial Planomicrobium and human‐associated bacteria ( Actinomyces , Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium ). Exposure to natural environmental microbiota may be beneficial to modulate shed human‐associated microbiota in an indoor environment.

Transport patterns and numerical simulation of heavy metal pollutants in soils of lead-zinc ore mines - Jie Cao; Cheng-yu Xie; Zhi-ru Hou (Journal of Mountain Science, 2021)

Transcriptome analysis of differentially expressed genes in chrysanthemum MET1 RNA interference lines - Dong-ru Kang; Yi Zhu; Shuai-lei Li; Peng-hui Ai; Muhammad Ayoub Khan; Hong-xu Ding; Ying Wang; Zi-cheng Wang (Physiology and Molecular Biology of Plants, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

New 40Ar/39Ar and (U-Th)/He dating for the Zhunuo porphyry Cu deposit, Gangdese belt, southern Tibet: implications for pulsed magmatic-hydrothermal processes and ore exhumation and preservation - Xiang Sun; Cheng-Biao Leng; Pete Hollings; Qing-Jie Song; Ru-Yue Li; Xiu-Quan Wan (Mineralium Deposita, 2021)

Anthropogenic Sound Exposure-Induced Stress in Captive Dolphins and Implications for Cetacean Health - Wei-Cheng Yang; Chi-Fang Chen; Yee-Chien Chuah; Chun-Ru Zhuang; I-Hua Chen; T. Aran Mooney; Jeff Stott; Myra Blanchard; I-Fan Jen; Lien-Siang Chou (Frontiers in Marine Science, 2021)
Many cetaceans are exposed to increasing pressure caused by anthropogenic activities in their marine environment. Anthropogenic sound has been recognized as a possible stressor for cetaceans that may have impacts on health. However, the relationship between stress, hormones, and cytokines secretion in cetaceans is complex and not fully understood. Moreover, the effects of stress are often inconsistent because the character, intensity, and duration of the stressors are variable. For a better understanding of how anthropogenic sounds affect the psychophysiology of cetaceans, the present study compared the changes of cortisol concentration and cytokine gene transcriptions in blood samples and behaviors of captive bottlenose dolphins ( Tursiops truncatus ) after sound exposures. The sound stimuli were 800 Hz pure-tone multiple impulsive sound for 30 min at three different sound levels (estimated mean received SPL: 0, 120, and 140 dB re 1 μPa) that likely cause no permanent and temporary hearing threshold shift in dolphins. Six cytokine genes (IL-2Rα, IL-4, IL-10, IL-12, TNF-α, and IFN-γ) were selected for analysis. Cortisol levels and IL-10 gene transcription increased and IFNγ/IL-10 ratio was lower after a 30-min high-level sound exposure, indicating the sound stimuli used in this study could be a stressor for cetaceans, although only minor behavior changes were observed. This study may shed light on the potential impact of pile driving-like sounds on the endocrine and immune systems in cetaceans and provide imperative information regarding sound exposure for free-ranging cetaceans.

Molecular epidemiological characteristics of echovirus 6 in mainland China: extensive circulation of genotype F from 2007 to 2018 - Wenjun Cheng; Tianjiao Ji; Shuaifeng Zhou; Yong Shi; Lili Jiang; Yong Zhang; Dongmei Yan; Qian Yang; Yang Song; Ru Cai; Wenbo Xu (Archives of Virology, 2021)
Echovirus 6 (E6) is associated with various clinical diseases and is frequently detected in environmental sewage. Despite its high prevalence in humans and the environment, little is known about its molecular phylogeography in mainland China. In this study, 114 of 21,539 (0.53%) clinical specimens from hand, foot, and mouth disease (HFMD) cases collected between 2007 and 2018 were positive for E6. The complete VP1 sequences of 87 representative E6 strains, including 24 strains from this study, were used to investigate the evolutionary genetic characteristics and geographical spread of E6 strains. Phylogenetic analysis based on VP1 nucleotide sequence divergence showed that, globally, E6 strains can be grouped into six genotypes, designated A to F. Chinese E6 strains collected between 1988 and 2018 were found to belong to genotypes C, E, and F, with genotype F being predominant from 2007 to 2018. There was no significant difference in the geographical distribution of each genotype. The evolutionary rate of E6 was estimated to be 3.631 × 10 -3 substitutions site -1 year -1 (95% highest posterior density [HPD]: 3.2406 × 10 -3 -4.031 × 10 -3 substitutions site -1 year -1 ) by Bayesian MCMC analysis. The most recent common ancestor of the E6 genotypes was traced back to 1863, whereas their common ancestor in China was traced back to around 1962. A small genetic shift was detected in the Chinese E6 population size in 2009 according to Bayesian skyline analysis, which indicated that there might have been an epidemic around that year.

A phenological object-based approach for rice crop classification using time-series Sentinel-1 Synthetic Aperture Radar (SAR) data in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Piero Toscano; Youg-Sing Cheng; Hong-Yuh Guo; Chien-Hui Syu (International Journal of Remote Sensing, 2021)

Genetic Analysis of Prosaposin, the Lysosomal Storage Disorder Gene in Parkinson’s Disease - Yong-Ping Chen; Xiao-Jing Gu; Ru-Wei Ou; Ling-Yu Zhang; Yan-Bing Hou; Kun-Cheng Liu; Bei Cao; Qian-Qian Wei; Wei Song; Bi Zhao; Ying Wu; Jing-Qiu Cheng; et al. (Molecular Neurobiology, 2021)

Regenerable, anti-biofouling covalent organic frameworks for monitoring and extraction of uranium from seawater - Yi-Di Wu; Wei-Rong Cui; Cheng-Rong Zhang; Ru-Ping Liang; Jian-Ding Qiu (Environmental Chemistry Letters, 2021)

Content and health risk assessment of heavy metals and polybrominated diphenyl ethers in fish from Songhua Lake (Jilin City), China - Mengnan Shen; Chunyu Kang; Tiehong Song; Hai Lu; Yuehong Wang; Bowen Yu; Ru Wang; Jie Cheng (Environmental Science and Pollution Research, 2020)

Machine learning approaches for rice crop yield predictions using time-series satellite data in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Horng-Yuh Guo; Youg-Sing Cheng; Shu-Ling Chen; Huan-Sheng Lin; Shih-Hsiang Chen (International Journal of Remote Sensing, 2020)

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

A new phenanthropyran and a new biphenanthrene from the rhizomes of Dioscorea septemloba and their antioxidant activities - Tao He; Yi Liu; Rui-Feng Xiong; Xiao-Yu Li; Shou-Feng Wang; Chun-Ru Cheng (Natural Product Research, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Correction to: Micropropagation of tree peony (Paeonia sect. Moutan): A review - Shu-Sheng Wen; Lan Chen; Fang-Yun Cheng; Ru-Nan Tian (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

The enhanced SO3 formation by alkali-metal sulfates from ash in the post-flame region during the combustion of high-alkali coal - Haiping Xiao; Qiyong Cheng; Hao Shi; Jian Li; Yu Ru (Environmental Science and Pollution Research, 2020)

Modified stepwise mini-incision microdissection testicular sperm extraction: a useful technique for patients with a history of orchidopexy affected by non-obstructive azoospermia - Peng Li; Chen-cheng Yao; Er-lei Zhi; Yuan Xu; Zhong Wan; Ying-chuan Jiang; Yu-hua Huang; Yue-hua Gong; Hui-xing Chen; Ru-hui Tian; Chao Yang; Liang-yu Zhao; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

An integrative assessment to determine the sediment toxicity of Kaohsiung Harbor in Taiwan: combining chemical analysis and cytotoxicity assay - Yun-Ru Ju; Chih-Feng Chen; Chiu-Wen Chen; Mei-Ling Tsai; Jia-Ching Wu; Cheng-Di Dong (Environmental Science and Pollution Research, 2019)

Recycled gypsum board acted as a mineral swelling agent for improving thermal conductivity characteristics in manufacturing of green lightweight building brick - Kung-Yuh Chiang; Huei-Ru Yen; Cheng-Han Lu (Environmental Science and Pollution Research, 2019)

Effect of metals on zooplankton abundance and distribution in the coast of southwestern Taiwan - Yun-Ru Ju; Wen-Tseng Lo; Chih-Feng Chen; Chiu-Wen Chen; Zhi-Ling Huang; Cheng-Di Dong (Environmental Science and Pollution Research, 2019)

The effects of negative air ions on cognitive function: an event-related potential (ERP) study - Chien-Heng Chu; Su-Ru Chen; Chih-Han Wu; Yung-Chao Cheng; Yu-Min Cho; Yu-Kai Chang (International Journal of Biometeorology, 2019)

Influence of Vitamin D Status and Mechanical Loading on the Morphometric and Mechanical Properties of the Mouse Tibia - Yong-Tao Lu; Zhen-Tao Cui; Han-Xing Zhu; Ru-Kun Ma; Cheng-Wei Wu (Journal of Medical and Biological Engineering, 2019)

Quantification of cardiac pumping mechanics in rats by using the elastance–resistance model based solely on the measured left ventricular pressure and cardiac output - Chih-Hsien Wang; Ru-Wen Chang; En-Ting Wu; Chun-Yi Chang; Hsien-Li Kao; Ming-Shiou Wu; Ya-Jung Cheng; Yih-Sharng Chen; Kuo-Chu Chang (Pflügers Archiv - European Journal of Physiology, 2019)

Antagonism of Ca2+-sensing receptors by NPS 2143 is transiently masked by p38 activation in mouse brain bEND.3 endothelial cells - Cing-Yu Chen; Mann-Jen Hour; Wen-Chuan Lin; Kar-Lok Wong; Lian-Ru Shiao; Ka-Shun Cheng; Paul Chan; Yuk-Man Leung (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Selenium (Se) Does Not Reduce Cadmium (Cd) Uptake and Translocation in Rice (Oryza sativa L.) in Naturally Occurred Se-Rich Paddy Fields with a High Geological Background of Cd - Bei-Bei Yang; Cheng Yang; Zong-Yuan Shao; Hao Wang; Shu-Ting Zan; Meng Zhu; Shou-Biao Zhou; Ru-Yi Yang (Bulletin of Environmental Contamination and Toxicology, 2019)

Spatial distribution and ecological risk assessment of sediment metals in a highly industrialized coastal zone southwestern Taiwan - Chiu-Wen Chen; Yee Cheng Lim; Chih-Feng Chen; Yun-Ru Ju; Cheng-Di Dong (Environmental Science and Pollution Research, 2019)

Enhancing tetrandrine cytotoxicity in human lung carcinoma A549 cells by suppressing mitochondrial ATP production - Louis W. C. Chow; Ka-Shun Cheng; Fai Leong; Chi-Wai Cheung; Lian-Ru Shiao; Yuk-Man Leung; Kar-Lok Wong (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Three new biflavonoids from the branches and leaves of Cephalotaxus oliveri and their antioxidant activity - Shu Xiao; Zhen-Qiang Mu; Chun-Ru Cheng; Jie Ding (Natural Product Research, 2019)

Satellite characterization of drought over cultivated areas in Central America - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Alex Castellón; Mario-Giovanni- Molina Masferrer; Luis-Eduardo-Menjívar Recinos (International Journal of Remote Sensing, 2018)

Alternations of Metabolic Profile and Kynurenine Metabolism in the Plasma of Parkinson’s Disease - Kuo-Hsuan Chang; Mei-Ling Cheng; Hsiang-Yu Tang; Cheng-Yu Huang; Yih-Ru Wu; Chiung-Mei Chen (Molecular Neurobiology, 2018)

Comparative chemical, taste, and functional components in different tissues of giant grouper ( Epinephelus lanceolatus ) - Chyuan-Yuan Shiau; Min-Hsien Hsu; Ann-Chang Cheng; Yu-Ru Huang (Journal of Aquatic Food Product Technology, 2018)

Chemical Characteristics of Different Tissues of Spectacled Caiman ( Caiman crocodilus ) - Yu-Ru Huang; Yung-Hsiang Tsai; Ching-Lu Liu; Wei-Zong Syue; Yi-Cheng Su (Journal of Aquatic Food Product Technology, 2018)

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Regulation of fine particulate matter (PM2.5) in the Pacific Rim: perspectives from the APRU Global Health Program - Chang-Fu Wu; Alistair Woodward; Ya-Ru Li; Haidong Kan; Rajasekhar Balasubramanian; Mohd Talib Latif; Mazrura Sahani; Tsun-Jen Cheng; Chia-Pin Chio; Nutta Taneepanichskul; Ho Kim; Chang-Chuan Chan; et al. (Air Quality, Atmosphere & Health, 2017)

Statistical features of eddies approaching the Kuroshio east of Taiwan Island and Luzon Island - Yu-Hsin Cheng; Chung-Ru Ho; Quanan Zheng; Bo Qiu; Jianyu Hu; Nan-Jung Kuo (Journal of Oceanography, 2017)

Evaluation on subcellular partitioning and biodynamics of pulse copper toxicity in tilapia reveals impacts of a major environmental disturbance - Yun-Ru Ju; Ying-Fei Yang; Jeng-Wei Tsai; Yi-Hsien Cheng; Wei-Yu Chen; Chung-Min Liao (Environmental Science and Pollution Research, 2017)

Improvement of aquaponic performance through micro- and macro-nutrient addition - Dongyun Ru; Jikai Liu; Zhen Hu; Yina Zou; Liping Jiang; Xiaodian Cheng; Zhenting Lv (Environmental Science and Pollution Research, 2017)

Overexpression of the ascorbate peroxidase gene from eggplant and sponge gourd enhances flood tolerance in transgenic Arabidopsis - Chih-Ming Chiang; Chiu-Chen Chen; Shi-Peng Chen; Kuan-Hung Lin; Li-Ru Chen; Yu-Huei Su; His-Cheng Yen (Journal of Plant Research, 2017)

Applying the strategy of light environment control to improve the biomass and polysaccharide production of Nostoc flagelliforme - Pei-pei Han; Shi-gang Shen; Hui-Yan Wang; Shun-yu Yao; Zhi-lei Tan; Cheng Zhong; Shi-ru Jia (Journal of Applied Phycology, 2017)

Peripheral Blood MicroRNA Expression Profiles in Alzheimer’s Disease: Screening, Validation, Association with Clinical Phenotype and Implications for Molecular Mechanism - Ru-Jing Ren; Yong-Fang Zhang; Eric B. Dammer; Yi Zhou; Li-ling Wang; Xiao-Hong Liu; Bei-Lei Feng; Guo-Xin Jiang; Sheng-Di Chen; Gang Wang; Qi Cheng (Molecular Neurobiology, 2016)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

Cytomolecular characterization and origin of de novo formed maize B chromosome variants - Ya-Ming Cheng; Ying-Ru Feng; Yao-Pin Lin; Shu-Fen Peng (Chromosome Research, 2016)

Sodium Channel Voltage-Gated Beta 2 Plays a Vital Role in Brain Aging Associated with Synaptic Plasticity and Expression of COX5A and FGF-2 - Yan-Bin XiYang; You-Cui Wang; Ya Zhao; Jin Ru; Bing-Tuan Lu; Yue-Ning Zhang; Nai-Chao Wang; Wei-Yan Hu; Jia Liu; Jin-Wei Yang; Zhao-Jun Wang; Chun-Guang Hao; et al. (Molecular Neurobiology, 2016)

Vertical profile, source apportionment, and toxicity of PAHs in sediment cores of a wharf near the coal-based steel refining industrial zone in Kaohsiung, Taiwan - Chih-Feng Chen; Chiu-Wen Chen; Yun-Ru Ju; Cheng-Di Dong (Environmental Science and Pollution Research, 2016)

Isolation and characterization of collagens from the skin of giant grouper ( Epinephelus lanceolatus ) - Cheng-Hong Hsieh; Chyuan-Yuan Shiau; Yi-Cheng Su; Yi-Han Liu; Yu-Ru Huang (Journal of Aquatic Food Product Technology, 2016)

Low-Dose Topical 5-Aminolevulinic Acid Photodynamic Therapy in the Treatment of Different Severity of Acne Vulgaris - Shi-qin Tao; Fei Li; Lei Cao; Ru-shan Xia; Hua Fan; Ying Fan; Hui Sun; Cheng Jing; Li-jia Yang (Cell Biochemistry and Biophysics, 2015)

Effects of Cu2+ and Zn2+ on growth and physiological characteristics of green algae, Cladophora - De-ju Cao; Pan-pan Xie; Juan-wei Deng; Hui-min Zhang; Ru-xiao Ma; Cheng Liu; Ren-jing Liu; Yue-gan Liang; Hao Li; Xiao-dong Shi (Environmental Science and Pollution Research, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Comparison of bacterial community structures of terrestrial cyanobacterium Nostoc flagelliforme in three different regions of China using PCR-DGGE analysis - Pei-pei Han; Shi-gang Shen; Shi-ru Jia; Hui-yan Wang; Cheng Zhong; Zhi-lei Tan; He-xin Lv (World Journal of Microbiology and Biotechnology, 2015)

Ameliorative effects of Bacillus subtilis ANSB01G on zearalenone toxicosis in pre-pubertal female gilts - Lihong Zhao; Yuanpei Lei; Yinghui Bao; Ru Jia; Qiugang Ma; Jianyun Zhang; Jun Chen; Cheng Ji (Food Additives & Contaminants: Part A, 2015)

Geochronological and geochemical constraints on the petrogenesis and geodynamic setting of the Qianlishan granitic pluton, Southeast China - Chun-Li Guo; Ru-Cheng Wang; Shun-Da Yuan; Sheng-Hua Wu; Bing Yin (Mineralogy and Petrology, 2015)

Cell-density-dependent manifestation of partial characteristics for neuronal precursors in a newly established human gliosarcoma cell line - Pei-Sen Yao; De-Zhi Kang; Xing-Fu Wang; Ru-Ying Lin; Zu-Cheng Ye (In Vitro Cellular & Developmental Biology - Animal, 2015)

Non-pulmonary vein foci induced before and after pulmonary vein isolation in patients undergoing ablation therapy for paroxysmal atrial fibrillation: incidence and clinical outcome - Hui Cheng; Yin-yin Dai; Ru-hong Jiang; Qiang Liu; Ya-xun Sun; Jian-wei Lin; Zu-wen Zhang; Shi-quan Chen; Jun Zhu; Xia Sheng; Chen-yang Jiang (Journal of Zhejiang University-SCIENCE B, 2014)

Metabolomic approach to optimizing and evaluating antibiotic treatment in the axenic culture of cyanobacterium Nostoc flagelliforme - Pei-pei Han; Shi-ru Jia; Ying Sun; Zhi-lei Tan; Cheng Zhong; Yu-jie Dai; Ning Tan; Shi-gang Shen (World Journal of Microbiology and Biotechnology, 2014)

Experimental Evaluation of the Sustainability of Dwarf Bamboo (Pseudosasa usawai) Sprout-Harvesting Practices in Yangminshan National Park, Taiwan - Chi-Cheng Liao; Chi-Ru Chang; Meng-Ting Hsu; Wak-Kim Poo (Environmental Management, 2014)

Two new cytotoxic iridoid esters from the rhizomes and roots of Patrinia heterophylla Bunge - Bo Yang; Ru-Bin Cheng; Yi-Qi Wang; Li Shen; Ru-Song Zhang (Natural Product Research, 2013)

Fine structure and primary sensory projections of sensilla located in the labial-palp pit organ of Helicoverpa armigera (Insecta) - Xin-Cheng Zhao; Qing-Bo Tang; Bente G. Berg; Yang Liu; Yan-Ru Wang; Feng-Ming Yan; Gui-Rong Wang (Cell and Tissue Research, 2013)

Imposex effects on the veined rapa whelk (Rapana venosa) in Bohai Bay, China - Li-hui An; Yanqiang Zhang; Shuang-shuang Song; Yue Liu; Zi-cheng Li; Hao Chen; Xing-ru Zhao; Kun Lei; Junmin Gao; Bing-hui Zheng (Ecotoxicology, 2013)

Effect of Sulforaphane on Growth Inhibition in Human Brain Malignant Glioma GBM 8401 Cells by Means of Mitochondrial- and MEK/ERK-Mediated Apoptosis Pathway - Tzuu-Yuan Huang; Weng-Cheng Chang; Miin-Yau Wang; Yun-Ru Yang; Yi-Chiang Hsu (Cell Biochemistry and Biophysics, 2012)

Cassiterite exsolution with ilmenite lamellae in magnetite from the Huashan metaluminous tin granite in southern China - Ru Cheng Wang; A-Peng Yu; Jun Chen; Lei Xie; Jian-Jun Lu; Jin-Chu Zhu (Mineralogy and Petrology, 2012)

Polycyclic aromatic hydrocarbons in household dust near diesel transport routes - Chung-Yih Kuo; Heng-Chun Chen; Fang-Ching Cheng; Li-Ru Huang; Po-Shan Chien; Jing-Ya Wang (Environmental Geochemistry and Health, 2012)

An upstream regulatory element confers orientation-independent enhancement of the TSG101 promoter activity in transformed cells - Shih-Fang Hsu; Yih-Gang Goan; Hsien-Yu Tsai; Yi-Ru Lin; Rue-Tsuan Liu; Jiin-Tsuey Cheng (Molecular Biology Reports, 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Reactive oxygen species-mediated PKC and integrin signaling promotes tumor progression of human hepatoma HepG2 - Chi-Tan Hu; Jia-Ru Wu; Chuan-Chu Cheng; Sindy Wang; Hsiao-Ting Wang; Ming-Che Lee; Ling-Jung Wang; Siou-Mei Pan; Tsu-Yao Chang; Wen-Sheng Wu (Clinical & Experimental Metastasis, 2011)

Functional characterization of a plasma membrane Na+/H+ antiporter from alkali grass (Puccinellia tenuiflora) - Xin Wang; Ru Yang; Baichen Wang; Guifeng Liu; Chuanping Yang; Yuxiang Cheng (Molecular Biology Reports, 2011)

Estimation of nested spatial patterns and seasonal variation in the longitudinal distribution of Sicyopterus japonicus in the Datuan Stream, Taiwan by using geostatistical methods - Yu-Pin Lin; Cheng-Long Wang; Chi-Ru Chang; Hsiao-Hsuan Yu (Environmental Monitoring and Assessment, 2011)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

Establishment of a transgene expression system for the marine microalga Schizochytrium by 18S rDNA-targeted homologous recombination - Ru-Bin Cheng; Xiang-Zhi Lin; Zhao-Kai Wang; Shan-Jun Yang; Hui Rong; Yong Ma (World Journal of Microbiology and Biotechnology, 2011)

PTEN status is related to cell proliferation and self-renewal independent of CD133 phenotype in the glioma-initiating cells - Ru-Bin Cheng; Rui-Juan Ma; Zhao-Kai Wang; Shan-Jun Yang; Xiang-Zhi Lin; Hui Rong; Yong Ma (Molecular and Cellular Biochemistry, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Exploring the molecular mechanisms of OSU-03012 on vascular smooth muscle cell proliferation - Wei-Wen Kuo; Jing-Ru Weng; Chih-Yang Huang; Chang-Hai Tsai; Wei-Hung Liu; Cheng-Hao Wen; Shih-Chang Tsai; Chieh-Hsi Wu (Molecular and Cellular Biochemistry, 2010)

Rubellimicrobium roseum sp. nov., a Gram-negative bacterium isolated from the forest soil sample - Yan-Ru Cao; Yi Jiang; Qian Wang; Shu-Kun Tang; Wen-Xiang He; Quan-Hong Xue; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2010)

Detection of circulating tumor cells in peripheral blood from patients with gastric cancer using microRNA as a marker - Hui Zhou; Jun-Ming Guo; Yan-Ru Lou; Xin-Jun Zhang; Fa-De Zhong; Zhen Jiang; Jia Cheng; Bing-Xiu Xiao (Journal of Molecular Medicine, 2010)

Differentiation of cryopreserved human umbilical cord blood-derived stromal cells into cells with an oligodendrocyte phenotype - Yong-Chun Luo; Hong-Tian Zhang; Hao-Yu Cheng; Zhi-Jun Yang; Yi-Wu Dai; Ru-Xiang Xu (In Vitro Cellular & Developmental Biology - Animal, 2010)

Origin of the Gangdise (Transhimalaya) Permian arc in southern Tibet: Stratigraphic and volcanic geochemical constraints - Quan‐Ru Geng; Zhi‐Ming Sun; Gui‐Tang Pan; Di‐Cheng Zhu; Li‐Quan Wang (Island Arc, 2009)
The well‐studied Mesozoic and Cenozoic volcanic rocks of the Gangdise Terrane, southern Tibet, are widely interpreted to have resulted from subduction of the Neotethys; however, Late Paleozoic volcanic rocks and their tectonic setting remain poorly studied. Based on new geological data, we carried out stratigraphical and geochemical analyses of Permian volcano‐stratigraphic sequences within an east–west‐trending, fault‐bounded zone of uplift in the central Gangdise Terrane. Sedimentary rocks in this area consist of platform carbonates and terrigenous clastic rocks that represent widespread shallow‐marine sedimentary basins developed around northern Gondwana. A regression or tectonic uplift event is recorded in Permian sedimentary rocks that show the local development of fluvial environments. The sedimentary succession contains evidence of two volcanic stages: a period of basaltic extrusions and younger explosive felsic magmatism. The first volcanic stage is Early and Middle Permian in age. Tholeiitic basaltic lavas are exposed around Maizhokunggar (Tangjia) and Lhunzhub in central Gangdise. The Lower Permian basalts are relatively enriched in MgO (4.58–12.19%), whereas the Middle Permian basalts are characterized by high Al 2 O 3 contents (11.75–21.22%). Rocks of both ages are enriched in large‐ion lithophile elements (LILE) and light rare earth elements (LREE), and show pronounced negative Nb and Ta anomalies. Total REE contents and light (LREE)/heavy (HREE) ratios increased from the Early to Middle Permian. Observed variations in initial Sr, Nd, and Pb isotopes ( 87 Sr/ 86 Sr i = 0.7013–0.7066, 207 Pb/ 204 Pb i = 15.53–15.63, and 208 Pb/ 204 Pb i = 38.04–38.64 for a given 206 Pb/ 204 Pb i ; εNd = +0.69 to −11.55) can be explained by crustal interaction with mantle sources, as is characteristic of metasomatism by slab‐derived fluids or assimilation and fractional crystallization (AFC) processes during magmatic evolution. The observed geochemical signatures, coupled with stratigraphic constraints, support the hypothesis that an initial arc formed during the Permian due to southward subduction of the Paleotethys, predating the well‐known Mesozoic arc preserved in the Gangdise Terrane.

SCA8 repeat expansion: large CTA/CTG repeat alleles in neurological disorders and functional implications - Yih-Ru Wu; I-Cheng Chen; Bing-Wen Soong; Shih-Huan Kao; Ghin-Chueh Lee; Shu-Yi Huang; Hon-Chung Fung; Guey-Jen Lee-Chen; Chiung-Mei Chen (Human Genetics, 2009)

Kazachstania wufongensis sp. nov., an ascosporogenous yeast isolated from soil in Taiwan - Ching-Fu Lee; Cheng-Hsu Yao; Yi-Ru Liu; Shuh-Sen Young; Ku-Shang Chang (Antonie van Leeuwenhoek, 2009)

Nearshore scavenging phenomenon elucidated by 234th/238u disequilibrium in the coastal waters off Western Taiwan - Ching-Ling Wei; Jing-Ru Tsai; Liang-Saw Wen; Su-Cheng Pai; Jen-Hua Tai (Journal of Oceanography, 2009)

Competitive displacement of the native species Bursaphelenchus mucronatus by an alien species Bursaphelenchus xylophilus (Nematoda: Aphelenchida: Aphelenchoididae): a case of successful invasion - Xin-Yue Cheng; Pei-Zhen Xie; Fei-Xue Cheng; Ru-Mei Xu; Bing-Yan Xie (Biological Invasions, 2009)

Compositions and source apportionments of atmospheric aerosol during Asian dust storm and local pollution in central Taiwan - Man-Ting Cheng; Wei-Chun Chou; Chia-Pin Chio; Shih-Chieh Hsu; Yi-Ru Su; Pei-Hsuan Kuo; Ben-Jei Tsuang; Shuen-Hsin Lin; Charles C.-K. Chou (Journal of Atmospheric Chemistry, 2008)

Detection of the key enzyme of alginate biosynthesis in Vibrio sp. QY102 - Xiao-Chong Shi; Qian-Hong Gong; Ru-Bin Cheng (World Journal of Microbiology and Biotechnology, 2008)

Exsolution lamellae in a clinopyroxene megacryst aggregate from Cenozoic basalt, Leizhou Peninsula, South China: petrography and chemical evolution - Xiao-Long Huang; Yi-Gang Xu; Ching-Hua Lo; Ru-Cheng Wang; Chuan-Yong Lin (Contributions to Mineralogy and Petrology, 2007)

PCR-RFLP analysis ofcytochrome b gene does not supportCoilia ectenes taihuensis being a subspecies ofCoilia ectenes - Qi-Qun Cheng; Da-Ru Lu (Journal of Genetics, 2005)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

Analyzing Hazard Potential of Typhoon Damage by Applying Grey Analytic Hierarchy Process - Szu-Ping Cheng; Ru-Yih Wang (Natural Hazards, 2004)

Analysis of heat-shock protein70 gene polymorphisms and the risk of Parkinson?s disease - Chiung-Mei Chen; Yuying Hsu; Sih-Jing Lin; Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Cheng-Kuang Wang; Yi-Ying Lin; Yih-Ru Wu; Hon-Chung Fung (Human Genetics, 2004)

Diverse apoptotic pathways in enterovirus 71–infected cells - Shih-Cheng Chang; Jing-Yi Lin; Lily Yen-Cheng Lo; Mei-Ling Li; Shin-Ru Shih (Journal of NeuroVirology, 2004)

Identification of genes involved in the host response to enterovirus 71 infection - Shin-Ru Shih; Victor Stollar; Jing-Yi Lin; Shih-Cheng Chang; Guang-Wu Chen; Mei-Ling Li (Journal of NeuroVirology, 2004)

Renal Tubule-Specific Expression and Urinary Secretion of Human Growth Hormone: A Kidney-Based Transgenic Bioreactor - Xinhua Zhu; Jin Cheng; Liwei Huang; Jin Gao; Zhong-Ting Zhang; Joanne Pak; Xue-Ru Wu (Transgenic Research, 2003)

Myosin light chain kinase modulates hypotonicity-induced Ca2+ entry and Cl– channel activity in human cervical cancer cells - Meng-Ru Shen; Paola Furla; Cheng-Yang Chou; Clive J. Ellory (Pflügers Archiv - European Journal of Physiology, 2002)

Seasonal dynamics of coastal ecosystems and export production at high latitudes: A modeling study - Ru Cheng Tian; Alain F. Vézina; Michel Starr; François Saucier (Limnology and Oceanography, 2001)
Export of organic matter from the surface to deeper waters often shows much smaller seasonal variations than primary production or nitrate‐based new production in mid‐ to high‐latitude marine systems. The mechanisms underlying this pattern remain poorly understood, but seasonal shifts in food web structure and dynamics have been implicated. We report here on an ecosystem modeling analysis of a high‐resolution (biweekly) time series of biomass, production, and export flux (sediment trap) measurements conducted in 1991 in Bonne Bay (Newfoundland). This time series shows the classical pattern of a spring bloom followed by a summer low biomass period, yet export is bimodal, with maxima during spring and late summer. The ecosystem model was forced by diagnostic vertical mixing calculations based on temperature and salinity records taken every 3 d and hourly wind data. The physical analysis indicated that the nitrate flux into the euphotic zone during summer was equivalent to that during the spring and fall seasons and accounted for half of the summer export. Statistical adjustments of the parameters of the ecosystem model indicated that strong production of dissolved organic carbon during the spring bloom, high temperature dependence of microbial activity, and physico‐chemical particle aggregation played key roles in explaining the remainder of the summer export. Seasonal changes in trophic pathways between spring and summer, such as a shift from a herbivorous to a microbial food web, played a comparatively smaller role. Our modeling analysis suggests that physical mixing processes and physico‐chemical aggregation processes are at least as important as shifts in food web trophic pathways in explaining the postbloom export flux in mid‐ to high‐latitude marine systems.

Swelling-activated taurine and K + transport in human cervical cancer cells: association with cell cycle progression - Meng-Ru Shen; Cheng-Yang Chou; J. Clive Ellory (Pflügers Archiv - European Journal of Physiology, 2001)

Volume-sensitive KCl cotransport associated with human cervical carcinogenesis - Meng-Ru Shen; Cheng-Yang Chou; J. Clive Ellory (Pflügers Archiv - European Journal of Physiology, 2000)

A Novel Spliced Transcript of Influenza A/WSN/33 Virus - Shin-Ru Shih; Piin-Chau Suen; Yuan-Shou Chen; Shih-Cheng Chang (Virus Genes, 1998)